The Transnational Institutionalization of the Ideal-Filipino-Hero of Overseas Filipino Workers (OFWs) in Vancouver, Canada - Calamba, Rincy Dominic C. (Simon Fraser University, 2026)
Overseas Filipino Workers (OFWs) in Vancouver, Canada experience ongoing systematic conditioning processes that are rooted in Philippine colonial history. Utilizing a multi-ethnographic approach and a framework drawn from Berger and Luckmann's concept of institutionalization and Foucault's biopower, I rethink the Filipino labour diaspora and interrogate how empire, labour, and migration, shape Filipino trajectories. Existing scholarship has documented the structural and working conditions of Filipino labour migration; this research contributes by foregrounding how these arrangements between the Philippines and Canada are lived, internalized, and reproduced through the institutionalized subjectivities of the Filipino citizen, the ideal migrant, and the Bagong Bayani (new hero). These subjectivities sustain systemic inequalities, coerce joining the labour diaspora, and render OFWs more vulnerable to exploitation while glorifying their sacrifices as noble contributions to family and nation. I further discuss the agency and resistance of OFWs, who actively reimagine their subjectivities and challenge these neocolonial paradigms.

Racial Discrimination at Work and Health of Canadian Workers: A Mixed Methods Study - Dalexis, Rose Darly (University of Ottawa, 2026)
Workplace racial discrimination remains a pervasive and harmful reality with profound implications for health and well-being. Drawing on evidence from three interrelated independent studies using both primary and secondary Canadian data, this research provides a comprehensive understanding of how workplace racial discrimination functions as both a social determinant of health and a chronic stressor contributing to adverse health outcomes and persistent health inequities. The findings demonstrate that workplace racial discrimination, manifesting through inequities in hiring, promotion, retention, and interpersonal interactions, increases the risks of significant psychological, physiological, and physical health outcomes for racialized workers. Experiencing workplace racial discrimination was strongly associated with heightened risks of anxiety, depression, stress and post-traumatic stress disorders, reinforcing mental health disparities across racialized groups. In addition, workplace racial discrimination increased perceptions of work-related stress, which in turn elevated the risk of diagnosed chronic conditions such as cardiovascular disease, Type 2 diabetes, high cholesterol, stroke effects and musculoskeletal disorders. Physiological assessments further revealed that recalling racial discrimination experiences contributes to dysregulated cardiovascular reactivity, including elevated systolic and diastolic blood pressure, as well as mean arterial pressure values above the normal range. Particularly severe forms of racial discrimination, implicating job loss, early retirement, undesirable resignation or leaves were linked to greater blood pressure increases. When incidents of racial discrimination were reported, especially when participants received acknowledgment of their experiences, physiological responses were attenuated. These results underscore the importance of personal action, recognition, accountability and institutional action in mitigating health risks. These findings underscore how workplace psychosocial stressors trigger harmful biological and physiological responses that may result in lasting health consequences. Taken together, this research highlights workplace racial discrimination as a critical public health concern that transcends individual experiences and reflects broader organizational inequities. Conceptualizing discrimination as a chronic stressor provides an essential understanding in addressing racial health disparities. The evidence points to the urgent need for organizational reforms, robust anti-discrimination policies, and workplace practices that not only prevent discrimination but also support the mental and physical health of racialized workers. Addressing workplace racism is not solely a matter of social justice; it is a public health imperative with the potential to reduce disparities, promote workplace equity, and improve the overall well-being of diverse populations.

“neither boy nor man”: Transnational Trade Identity in Canada’s Typographical Trade Press, 1860-1900 - Pelletier, Sarah Françoise (Carleton University, 2026)
“‘neither boy nor man’: Transnational Trade Identity in Canada’s Typographical Trade Press, 1860-1900” is situated at the intersection of literary, periodical, print historical, and labour studies. Examining the eight printing trade journals produced in central and eastern Canada during the later nineteenth century (Ontario, Quebec, and New Brunswick), this project contributes a Canadian dimension to extant scholarship on printing trade journals, which has mostly attended to British and American publications. This study of Canadian printers’ trade journals offers important insights for understanding how the Canadian trade was situated as a node within the printing trade’s transnational network. Journeymen hand typesetters working in the Canadian newspaper trade of the later nineteenth century identified various threats to their aristocratic trade identity: apprentices, amateur labourers, and tramp printers; rising literacy rates and the middle-class worker; women; the work of Black, Indigenous, and Chinese compositors; and the introduction of machines in typesetting. Situating these perceived threats within the context of local and transnational/transatlantic histories of printing, I demonstrate how journeymen used narrative, poetry, correspondence, humour, and visual devices as defensive tools to reinforce and protect the trade’s aristocratic labour identity and to associate the work of typesetting with masculinity, skill, superior intelligence, and whiteness. Due to Canada’s position within the British Empire and its proximity to the United States, the exclusionary discourses that Canadian journeymen compositors cultivated and circulated were shaped by both national and transatlantic labour discourses. Further, I argue that these representational strategies were largely misplaced, given that the actual threats of deskilling and technological unemployment resided not with half-trained compositors, women, and other apparent dangers to the trade, but in the structural conditions of print capitalism and of waged labour more generally. The textual and historical analysis of the labour discourses found within Canadian printing trade journals that I present in this dissertation demonstrates that Canadian journeymen were ultimately concerned about what changes to the economic and technological landscape of their trade at the end of the century would mean for their status as men whose identities were intrinsically tied to waged work, skill, and craftsmanship.

Union Houses & Social Factories: Hauntological Successors to Sites of Material Production - Teed, David (Dalhousie University, 2026)

Migrant Stories, Industry Narratives: A Critical Discourse Analysis on Migrant Labour in Canadian Agriculture - Helps, William Louis (University of Guelph, 2025)
Since the onset of the COVID-19 pandemic in early 2020, many Canadians have become newly aware of problematic power imbalances and potential for abuse under the Temporary Foreign Worker Program (TFWP), which forms a key component of the Canadian agri-food workforce. The increased attention brought to some of the negative outcomes of Canada’s agricultural migrant labour system appear to have prompted an industry response, including through the More than a Migrant Worker initiative launched by a collection of agri-food industry groups. This dissertation presents the results of research on texts gathered from the More than a Migrant Worker initiative. Critical discourse analysis was used to identify themes, arguments, and rhetorical techniques the initiative employs to convey a narrative about migrant farm workers to the public. Findings indicate that these agri-food industry groups have adopted a defensive stance in response to critiques of migrant labour policies, as demonstrated by the discourse’s treatment of themes such as migrant workers’ and their families’ financial motivations, the purported necessity of migrant labour to sustain Canadian food production, and the formal rights and protections built into the TFWP, combined with a de-emphasis of the evidence of persistent systemic issues in the protection of migrant workers from mistreatment. The findings support a theoretical framework of managed migration based on a combination of Labour Market Segmentation Theory and the New Economics of Labour Migration, in which the devaluation of agricultural work in the domestic labour market and the disruption of traditional economies by neoliberal global market forces generate a demand for and supply of migrant labour, respectively. The paper’s conclusion provides directions for further research to expand academic knowledge of migrant labour discourse and migration theory, as well as recommendations for policy makers, the agri-food industry, and advocacy groups for productive policy discussions that find consensus on ways to protect and improve the conditions of migrant farm workers.

Neoliberal Policies and Rhetoric in the Struggle for Ontario Gig Workers' Rights - Abernethy, Zoe Ming Hui Gibbons (Carleton University, 2025)
How have neoliberal discourses of the gig economy shaped the terrain of gig worker organizing in Ontario? This thesis interrogates and contextualizes Uber’s efforts to legitimize and further expand its operations in Ontario during and after the COVID-19 pandemic, focusing on the centrality of its appeals to (and reproduction of) workers’ entrepreneurial common sense in these endeavors. Drawing on ten-semi structured interviews with current and former Uber drivers and delivery workers, it explores the contradictory form of independence experienced by platform-mediated gig workers, reflecting on the significance of gig work being perceived as the “least worst option” within the contemporary labour landscape.

The Intersection of Work and Care: Exploring the Facilitators and Barriers of Maternal Employment in Canada - Abraham, Haneen Alia (University of Alberta, 2025)
Since the 1970s, many OECD countries have seen a significant increase in maternal employment rates. In cross-national comparison, Canada has high maternal employment rates, but lags behind some Nordic and East European countries. Within this context, this study explores how larger social, cultural and policy environments shape mothers' employment experiences, challenging the notion that women prefer to opt out of the labour force when they have children To conduct this analysis, I drew on focus groups (n=19) and individual interviews (n=39) with 58 mothers in Canada with preschool children in the province of Alberta. The key finding from this study was that the majority of mothers, despite wanting to continue their careers alongside parenthood, experienced challenges integrating unpaid and paid work. To navigate these challenges, mothers employed various strategies, including seeking flexibility at work, reducing work hours, or opting out of employment. Yet, many remained ambivalent regarding their employment arrangements. I detail the ways in which paid parental leave and childcare policies acted as facilitators or barriers to mothers’ labour force participation. Overall, the findings indicate that current policies are not sufficient to support mothers in the labour force. This study adds to a body of Canadian literature that examines how barriers such as pervasive gender norms in the workplace and households, and workplace inflexibility, create barriers to mothers’ labour force participation and impact mothers’ experiences in the labour market.

Technological Change and an Aging Workforce: Investigating the Career Experiences of Older Workers - Adeniyi, Judah I. (Memorial University of Newfoundland, 2025)
This dissertation examines the intersection between two significant economic and societal challenges: an aging workforce and rapid technological change. The aging workforce is a growing concern, particularly in Canada, where the population of older workers (55 years and older) surpasses that of younger entrants (15 to 24 years). This demographic shift, already contributing to labour shortages in key sectors like manufacturing and healthcare, poses risks to labour participation rates and the stability of healthcare and pension systems (Acemoglu & Restrepo, 2017; Maestas et al., 2016). Given the projected exodus of older workers and limited incoming replacements, scholars and practitioners advocate for delayed or phased retirements to mitigate talent shortages. Simultaneously, technological change reshapes work, presenting opportunities and challenges, especially for older workers who may find adapting to new technologies daunting. This environment makes it critical to understand how technology affects older workers' experiences, including their retirement intentions. I conducted two studies to better understand the impact of technology and technological changes on older workers' work experiences. In Study One, I conducted a systematic literature review to synthesize existing research on technology's impact on older workers, with a comprehensive analysis of 121 articles, including both peer-reviewed (n=82) and grey literature sources (n=39). Thematic analysis revealed key areas in the current literature, such as socio-demographic factors, training and development, and retirement planning. The results of this study also included descriptive insights on journals, methodologies, regions, and publication dates, highlighting 14 important research gaps. These gaps guided recommendations for future studies, which aim to address the implications of technological innovations on an aging workforce. In the second study, I empirically examined the relationship between technological change and older workers' retirement intentions using a sample of 361 participants. Testing a moderated mediation model grounded in the Job Demand-Resources (JD-R) theory, I analyzed burnout and perceived work ability as serial mediators alongside moderating factors of computer self-efficacy, technological training, and organizational justice. Findings accentuate the complex interplay of burnout, work ability, and retirement intentions, emphasizing that burnout negatively impacts work ability, which in turn influences retirement intentions. Notably, technological training significantly moderated the relationship between burnout and work ability, reinforcing its role as an important factor shaping older workers' capacity to adapt within technologically evolving work environments. Ultimately, this dissertation provides valuable implications for both theory and practice. The findings from both studies provide important directions for the successful integration and retention of older employees in the rapidly changing technological work environment, as well as for creating a supportive work environment for them.

"Everything I Know Is Canada": Migrant Farmworkers and the Making of Homes Across Borders - Baeza Martinez, Regina (Simon Fraser University, 2025)
Canada is wholly reliant on migrant farmworkers who provide cheap labour while being barred from a wide range of rights and services, including pathways to permanent residency (Sharma, 2012; Satzewhich, 1990; Basok, 2002). Whereas most of the research on migrant farmworkers follows a deficit model, my thesis focuses on collective agency by asking: how do migrant farmworkers create a sense of home in Canada while unable to settle permanently in the country? Drawing from interviews and participant observation conducted in Guatemala and Canada, I show how migrant farmworkers exceed the boundaries of the farms where they live and work, forging their own modes of social organization using Indigenous Mayan cultural logic. Framing migrant farmworkers as strategic boundary-crossers, I highlight how they breach farm borders and, through the exchange of ideas across nation-states, inspire new migration journeys.

Thwarted and Delayed: Three Eras of Legislating Labour Rights in the Ontario Public Service, 1867-2017 - Carson, Thomas Jonathan (York University, 2025)
Seeking to understand why public servants took so long to achieve labour rights—particularly the right to strike—compared to those in the broader economy, this dissertation explores the historical evolution of labour relations within the Ontario Public Service (OPS) from 1867 to 2017. Through an examination of the interplay between institutions and broader socio-economic and political forces, viewed through a critical institutionalist framework, this study argues that the development of OPS labour relations is defined by three distinct eras. The first era, from Confederation until the 1960s, was dominated by the principle of parliamentary sovereignty, which limited the labour rights available to public servants. The second era, from the 1960s to the 1990s, saw the ideology of the governing party as the primary dynamic, with party ideology playing a significant role in the emergence of public servants’ right to strike. Starting in the 1990s, the third era saw the rise of neoliberalism shift the focus of governments of all partisan stripes toward cost containment. As a result, this era was marked by hard bargaining and practical constraints on the feasibility of the strike option. This study demonstrates how these primary factors, along with other influences such as worker militancy and class relations, have shaped the long development of the OPS labour relations regime. The dissertation concludes that, despite significant legislative changes, the government has nevertheless retained considerable control over the material outcomes of the public service labour relations system.

Foodwork as Relationality: Labour and the Creation of Culinary Placemaking - Chartrand, Stephanie (University of Toronto, Ontario Institute for Studies in Education, 2025)
This thesis explores the concept of culinary placemaking through the lens of Global Political Economy (GPE), focusing on how foodwork functions as a relational practice that shapes social, cultural, and economic spaces. It examines the relationships among food, labour, and place, emphasizing the ways in which workers transform culinary environments into meaningful places through their physical, emotional, and creative contributions. Drawing on existing literature, the research highlights how neoliberal policies have commodified food and labour, leading to increased precarity and alienation for food workers. Despite these challenges, culinary workers actively resist the pressures of globalization by fostering localized food systems, emphasizing cultural and social engagement, and envisioning alternative economic models such as cooperatives and farm-to-table initiatives. This thesis finds that culinary placemaking not only resists commodification but also offers opportunities for social cohesion, cultural expression, and economic resilience. Furthermore, the research touches upon the gendered dimensions of culinary labour, demonstrating how workers navigate power dynamics within professional kitchens and community food spaces. Future research directions include exploring the evolving role of consumers in culinary placemaking, addressing labour precarity through policy interventions, and investigating how Indigenous economies contribute to decolonial approaches to food sovereignty. By situating foodwork within the broader political and economic context, this thesis contributes to a deeper understanding of the transformative potential of culinary labour in fostering inclusive, sustainable, and culturally resonant food spaces.

Soldiers in Capitalist Society: Critique of the Labour of Political Violence - Chorley Foster, Jasmine (University of Toronto, 2025)
This dissertation critiques the soldier in capitalist society as a category of social labour that produces the state capacity for political violence. Identifying soldiering labour is essential to historicizing how this social capacity of labouring people is fetishized as the military power of the state. From the perspective of this project, the substance of the labour of the soldier is affected but not resolved by a resolution of form (such as the standing army, or transition from a draft to an all-volunteer army). What is discovered through historical and theoretical analysis and soldiers’ struggles themselves, is that historical class struggles in the military can be read as contests for political sovereignty over the labour of political violence: literal power over cooperative labour, not merely over institutions, or freedom in the ‘spheres’ of politics and economics. It captures the necessity of emancipation in one as a condition of the emancipation of the other; and that of the soldier as a condition for everyone else’s so long as we are to be concerned with the entirety of human life and not the exception of a single nation-state’s population.

Legal Silence, Worker Suffering: Law, Electronic Workplace Surveillance, and Amazon Warehouse Worker Injuries in Ontario - Del Riccio, Jennifer (University of Toronto, 2025)
In the American and Canadian warehouses of the e-commerce giant Amazon, electronic workplace surveillance (“EWS”) technologies permit the unprecedented quantification and datafication of worker activity, enabling the setting and enforcing of unsafe productivity ‘quotas’ that lead to serious occupational injuries for warehouse workers. In this paper, I consider the role of Canadian law – namely, the employment, privacy, and occupational health and safety legal regimes in the province of Ontario – in enabling, and in potentially constraining, this phenomenon in Ontario’s Amazon warehouses. In doing so, I identify the ‘legal silence’ that shapes the lived experiences of Amazon warehouse workers in Ontario; contribute to the emerging theorization, particularly from a legal perspective, of EWS as a factor impacting workers’ physical health; and propose legal reforms that would improve the safety and well-being of Amazon warehouse workers – and other similarly-situated workers – across the province.

"When you are accepting money you have to do as you are told:" The CAHA/NHL Relationship and the Rise of the Professional Sponsorship System, 1936-1952. - Di Gravio, Michael (Western University, 2025)
This thesis undertook an interpretivist historical analysis of the publicly available Canadian Amateur Hockey Association (CAHA) meeting minutes from 1936 to 1952. A Foucauldian lens of disciplinary power was used to answer the research question: how was the National Hockey League (NHL) able to develop a professional sponsorship system within the CAHA following World War II, and what effects did this have on Canadian minor hockey. The results found that following the signing of the CAHA/NHL agreement, the NHL exercised its disciplinary power over the CAHA members to instill in them what Foucault termed ‘docility.’ The birth of the professional sponsorship system following WWII was a result of this disciplining and docility. Through this system, the NHL brought its disciplinary technologies directly to bear on Canadian minor hockey and gained the ability to control players' rights from ages as young as twelve years old.

"The Gilt-Edged Class": American and Canadian Telegraphers' Bodies and Work - Feagan, Michael (Western University, 2025)
This dissertation examines the lives and work of American and Canadian telegraph operators from 1870 to 1929. While historians have studied the telegraph as a technology and a business, few have integrated telegraphy with histories of class, gender, or the human body. Integrating the bodily turn means recognizing the physicality of telegraph work. This dissertation centres the bodies of telegraph operators and seeks to contextualize those bodies within the larger technological and corporate systems in which they were embedded. Operators’ class identities have often been ambiguous or misunderstood. I argue that telegraph work was real, physical work, in a way that has too often been elided, and that it is important to see operators as part of the working class. Ultimately, this dissertation demonstrates the ways in which human bodies and human labour can be erased within large technological networks. I explore the historical significance of that erasure and its relevance for understanding the precarity of labour in high-tech industries today.

Conflict And Solidarity Between Anti-Colonial Environmentalism, Indigenous Anti-Pipeline Resistance, and Labour - Golkar, Niloofar (York University, 2025)
Climate change has reached crisis mode, and confronting it requires confronting corporations, economic planning, policies that exacerbate this process, and social relations that enable such policies and economic paths. This dissertation shows how settler colonialism in Canada revolves today around extractivism. This fact makes the struggle for land critical and highlights how Canadian nationalism is an obstacle to Indigenous solidarity and environmentalism. In 2020, the Shut Down Canada movement that started from Wet'suwet'en territories against building the CGL pipeline on their land, which was a scale-up from the Idle No More movement, underscored the importance of the Land Back movement for environmental justice. Its tactic of shutting down critical infrastructures was the largest scale in Canada's recent history of Indigenous resistance at the time. The well-documented militarized attacks on Wet'suwet'en unceded territories creates a dilemma that should concern every activist. At the same time, the impressive organizing efforts that started from Unist'ot'en as a space of resistance provide lessons for every movement. The case of the CGL pipeline and Wet'suwet'en resistance puts us at the conjuncture of three movements: the issue of solidarity between labour, anti-capitalist Environmentalists and the Indigenous movement. In this dissertation, I strategically explore possibilities for building strong Indigenous-environmentalist-labour solidarity. Through extensive policy analysis of the critical infrastructure risk management approach and media analysis of the CIRG task force, I explore a hidden link between the security arm of one of the largest global investment corporations, KKR, RCMP, and TC Energy executives. The government's risk management approach has enabled such a link, which facilitates and encourages conversations between the involved actors. The state's claim to the so-called public/Canadian interest in pipelines is of utmost importance to this dissertation. The concept of Canadian interest works as a settler colonial and national ideology of governing; historically and presently, the concept creates an umbrella that includes the Canadian working class as it excludes Indigenous communities, along with the processes of reproducing nature and non-capitalist forms of economy that many radical environmentalists try to create through commons. A lack of land-based analysis of the situation of working-class people in Canadian labour has turned the labour movement into a more economistic version of trade unionism, one that does not actively oppose Canadian nationalism.

Depicting Mexican Labour for/within Contemporary Canadian Imperialism: Photography, Participation, and Power - Gonzalez Teran, Anahi (Western University, 2025)
This studio-based dissertation project emerges from my engagement with the politics of representation of labour and visual culture. Rooted in my experience as a Mexican artist living in Canada, the project examines how Mexican labour is framed through photography, performance, and installation. These themes form the central focus of my research, which moves across Lands and disciplinary forms to investigate how systems of power shape the representation of Mexican workers and how irony can be used as a tool to question dominant narratives. The written component of this dissertation forms part of an interdisciplinary thesis that includes a series of exhibitions and performances carried out between 2021 and 2025 in today’s Mexico and Canada. The artworks, presented across artist-run centres in Ontario and as outdoor installations, use staged photographs, installations, participatory works, to examine labour, value, and exchange. These pieces were shown in the province of Ontario, Canada and the state of Coahuila, Mexico. My thesis engages with a range of theoretical frameworks to support and extend my artistic practice. Drawing from visual culture theory, performance studies, and participatory art discourse, I incorporate the work of theorists such as Stuart Hall, Jacques Derrida, and Claire Bishop, among others. As a whole, this dissertation considers how visual and performance-based practices can challenge representations of Mexican labour across Lands and reflect on the systems that shape the movement of people, goods, and images. The written component includes five chapters, followed by photographic documentation of the works and exhibitions produced during my doctoral studies. Together, the writing and the artworks propose a critical reflection on contemporary labour and visual politics.

Labour, Migration and Resistance: The Legacy of INTERCEDE in Domestic Workers Advocacy in 1980s Ontario. - Haruna, Jamila (Trent University, 2025)
In 1980s Ontario, racialized migrant domestic workers faced systemic exploitation, precarious immigration status, and exclusion from labour protections, reinforced by provincial and federal policies that devalued domestic labour. This thesis examines how INTERCEDE, a Toronto-based coalition, challenged these structural inequalities. Employing an intersectional approach, this study reveals how race, gender, immigration status, and class collectively marginalized migrant care workers. Drawing on extensive primary sources, it analyzes INTERCEDE's influence on major policy changes, including reforms to the Foreign Domestic Movement (FDM) program and to provincial labour laws. The thesis argues that while INTERCEDE efforts contributed to securing significant, albeit often fragile, victories, these gains highlighted both the power of activism and the persistent challenges under neoliberal regimes. It contributes to feminist labour history, migration studies, and care work scholarship by demonstrating how organized resistance reshaped Canadian policy and contested institutionalized marginalization.
Keywords: Care activism; Care work history; Feminist labour history; History; Labor relations; Migrant domestic workers; Resistance; Womens studies

Transnational Circuits of Precarity: A Qualitative Examination of Temporary Worker Wellbeing in Manitoba - Huynh, Anthony (University of Manitoba, 2025)
Background: In western Canada, Manitoba is a critical hub for a large population of migrant workers. Usually with limited English or French language ability and possessing limited rights and protections under the current TFWP, Temporary foreign workers (TFWs) are often tied to a single employer, leaving them vulnerable to employer abuse and the under-reporting of workplace injuries and illnesses due to the threat of deportation. Within the context of the COVID-19 pandemic, when my dissertation research began, the many cases seen among TFWs in Manitoba raises additional important public health questions on the health and wellbeing of migrant workers in Manitoba that I discuss in this dissertation. Methodology: In close collaboration with Migrante Manitoba (MB), I conducted a qualitative study to explore the precarious lives of migrant workers during the COVID-19 pandemic. I virtually interviewed 20 migrant workers who entered Canada through the TFWP, employed either as seasonal agricultural workers (n=7) or TFWs (n=13). Thirteen TFWs came from Philippines and seven farmworkers from Mexico (n=6) and Jamaica (n=1). Theoretical contribution: I developed the notion of transnational circuits of precarity to understand the multiple temporal-spatial layers of precarity that migrant workers encounter along their journeys to Manitoba. This multivalent concept is comprised of the following interconnected pieces: 1) a broader political economic “force-field” that compels the movement of human labour resources from the global South to the global North; 2) the rigid and regulated pathway put in place to ensure workers arrival at their work destinations; 3) the process of making “model minorities” through training programs that ensure the “smooth” transition of workers in their host country; and 4) the affective economy that is fueled by workers’ hopes, dreams, and desires. Altogether, these seemingly disparate processes articulate to produce complex temporal and spatial realities that shape the precarious trajectories of migrant workers. Such a paradigm shift away from the narrow temporal and spatial limits of a focus on “occupational health hazards” will be critical if workers are to realize any meaningful and substantive changes to their overall physical and mental well-being.

In What Ways Does a Lack of Status Influence the Psychosocial Well-Being of Non-Status Migrants in Alberta? - Karnjanavijaya, Jakkapan R. (University of Alberta, 2025)
Canada is a country whose economy benefits considerably from migrant workers in the Temporary Foreign Worker Program (TFWP). With little protection from workplace exploitation, as well as unclear and constantly changing immigration policies, migrant workers often lose their legal immigration status due to conditions out of their control, becoming non-status. Living in the shadows and without access to most publicly funded services, non-status migrants experience a myriad of chronic daily stressors. In partnership with non-status community members, this Community-based Participatory Research project explores the question, “In what ways does a lack of status influence the psychosocial well-being of non-status migrants in Alberta?”. Both non-status migrants and service providers participated in semi-structured interviews, while a group of service providers working in mental health also participated in a focus group interview. The interpretation of this study’s findings was guided by the socio-ecological systems framework. Non-status realities were described from the perspective of both non-status migrants and service providers. Findings included insights into how the TFWP creates systemic vulnerabilities for migrant workers and facilitates the loss of immigration status. This lack of status led to a scarcity of access to most basic services and resources, leading to significant detrimental impacts on psychosocial well-being. This produced internalized experiences of shame and un-belonging, as well as a range of deleterious mental health outcomes. Furthermore, the impacts associated with a lack of access were significantly exacerbated by a discriminatory and hostile sociopolitical environment. Recommendations centered around the inclusion of non-status migrants in collaborative partnerships with service providers and policymakers alike. In light of these findings and recommendations, the implications for counselling psychology practice are also illuminated.

Collective Labour in a Capitalist Market: The Historical Struggle to Secure a Place for Worker Cooperatives in the Canadian Political Economy. - Kinsey, Simon Wilson (Carleton University, 2025)
This thesis seeks to understand the historical conditions that have relegated worker cooperatives to the periphery of the Canadian political economy. It begins with a theoretical exploration of the relationship between worker cooperatives and capitalism, highlighting two key dynamics: 1) worker cooperatives are a form of collective property that allow workers to secure their subsistence outside of the wage-labour market; 2) worker cooperatives can serve a wide range of interests depending on the subjectivities of the worker-members and the objective conditions of their political-economic environment. This framework is then used to examine subjective and objective considerations in the context of Canadian worker cooperatives, with a focus on the emergence of the contemporary sector in the 1970s and 1980s. Material need has at times produced upswings of grassroots momentum, but this momentum has struggled to sustain itself in the absence of support from major institutions of the Canadian political economy.

Navigating the Gendered Landscape: The Impact of Institutional Participation and Professional Culture in Shaping Inequality - Mogoşanu, Andreea (University of Toronto, 2025)
The Gender Revolution significantly improved women’s status, but recent progress towards equity is “uneven and stalled” (England 2010:149). This dissertation uncovers the complex role of institutional processes in shaping the evolution and persistence of gender inequality. The first study offers a macro-level analysis trends in men and women’s perceptions of mastery across the life course of different cohorts. Perceptions of mastery —control over one’s life— reflect differences in status and gendered notions of agency (Connell 1987; 2005). Institutional participation —educational achievement and employment levels— is key in shaping movement towards and away from gender equality. While high levels of education and employment lead to converging perceptions of mastery, the effect of institutional participation is strongly gendered: women benefitted more from education, while men are penalized more when working less than full-time. Workforce participation emerged as a key driver of men’s higher perceptions of agency in younger cohorts. Drawing on the legal profession as a case study, subsequent studies highlight the role of workplace culture in shaping gender inequality. Using longitudinal data on private sector lawyers, the second paper finds norms of hegemonic masculinity —measured as technical competence, authoritative leadership, work devotion, breadwinner status, and individual preferences— (re)create wage inequality across the earnings distribution. The analysis further uncovers a hierarchy of valuation based on gender and parental status, as fathers earn the highest wage premiums, followed by mothers; women without children earn the least after controls. The final paper investigates how perceptions of professional fit —signaled by professional role confidence (PRC)— shapes perceptions of job security among early-career lawyers. The legal profession is marked by a ‘masculine mystique’ that challenge female lawyers’ PRC —measured as expertise confidence and career fit. Findings indicate that men derive higher perceptions of job security for the same levels of PRC, explaining women’s lower perceptions of job security. Professional fit therefore reinforces gender inequality, possibly through women’s awareness (but not internalization) of their lower status in law. This dissertation provides a nuanced understanding of gender inequality, with institutional participation and culture emerging as key mechanisms shaping the dynamic evolution of gender inequality.

Performing the Subject-Self: A Critical Exploration of Sex Worker Resistance and Activism in Canada - Murray, Julie Anne Cordeiro (Université d'Ottawa / University of Ottawa, 2025)
The contemporary movement for sex workers' rights emerges from a lengthy and complex legal history of sex workers challenging dominant discourses that frame prostitution as a public nuisance, moral offence, and violence against women. The existing literature demonstrates that sex workers and sex work activists resist oppressive and reductive discourse via community-based initiatives, lobbying efforts, and strategic litigation such as the successful constitutional challenge against Canada's prostitution laws in 2013 (Canada (Attorney General) v. Bedford, 2013). However, there is a significant gap in understanding how sex workers and sex work activists enact resistance through embodied performance. As such, this thesis explores the ways in which sex worker rights activists resist dominant discourse and troubling public perceptions through symbolic communication and attire during protests. To this end, this research builds a conceptual framework that puts resistance literature in conversation with key theoretical insights from Michel Foucault and Judith Butler. Based on 143 publicly accessible images of sex worker rights protests in Canada between 2013-2023, a qualitative visual content analysis is deployed to examine how sex workers and sex work activists enact resistance through what the author calls the performance of the subject-self. The findings reveal how the subtle, creative, and symbolic aspects of sex work activism are serious and significant forms of political expression.

Bridging the Gap: Exploring the Experiences of South Asian Women Immigrant Teachers in Toronto - Omar, Rozalina (University of Toronto, Ontario Institute for Studies in Education, 2025)
In this dissertation, I share the voices of South Asian women immigrant school teachers living in Toronto. In this era of global mass migration and the increasing number of women immigrants, I argue that it is important to examine how gender and race affect racialized immigrant women’s working experiences. Historically, racialized immigrant women in Canada have faced various forms of discrimination in the labour market: not only are their previous qualifications and experiences devalued in the job market, but after entering the job market, racial and gender identity remain a concern in their professional lives (Crea-Arsenio et al. 2022; Premji et al. 2014). While scholars have highlighted the common labour market barriers, the struggles of South Asian women when facing these challenges in seeking a specific career do not get enough attention in the academic world. A significant number of South Asian women must engage in precarious jobs that are not consistent with their skills and qualifications. Here, I recruited South Asian immigrant women who hold a teaching certificate in Ontario and are coping with the secondary-education labour market and/or other related jobs in Toronto. Guided by a Critical Race Feminist perspective, I used interpretive inquiry as a research methodology to facilitate participants telling their struggles, challenges, and negotiations of their everyday lives while living in a large urban center like Toronto. My analysis of this research shows that these South Asian groups of women must overcome barriers that are similar to many other non-racialized female professional immigrants - but as racialized female immigrants, they also face more challenges in accessing and coping with their current professions. My findings suggest that policymakers should focus on an adaptable labour-market transition process for these professional groups after migration. This could also be helpful for other racialized groups in general. Promulgation to eliminate systematic barriers through various forms is needed to decrease the substantial existence of teacher diversity gap in Ontario. Therefore, this study extends the available literature by considering voices of racialized immigrant women, thereby addressing some existing gaps in policy framework.

Realities of Precarity in Canada's Seasonal Fields: Struggles, Advocacy, and Restricted Spaces and Voices - Patterson, Dominica (University of Ottawa, 2025)
The following thesis examines the complex reality of temporary migration within Canada's agricultural sector by investigating the Seasonal Agricultural Worker Program (SAWP). The relevance of this inquiry hosts far-reaching implications for not only the wellbeing of migrant workers, but for the Canadian food-system, as well as migrant sending states. Furthermore, this research contributes additional knowledge and insights regarding the evolving interconnections between the climate and migration crisis that host critical impacts for Canada and the world moreover. In analyzing the impact of the SAWP on migrant workers' lives through two case studies, the project explores the interplay between climate change, globalization, neoliberalism, and liberalization in shaping the precarity faced by migrant workers in Canada. Despite the commonly advertised benefits of the SAWP, the study finds that structural barriers and power imbalances limit the realization of these benefits for migrant workers. The study ultimately explores the divided calls for reform across the sector, revealing the influence of widespread industry malpractice, and the presence of entrenched power hierarchies that have served to dominate the scope and direction of change. The research finds that the SAWP's structure and the broader context of inequalities related to globalization and neoliberalism hinder migrant workers' ability to leverage their assets and improve their livelihoods in Canada.

Harassment and Violence faced by Latinas on Ontario Construction Industry work sites - Ratsch, Valeria (University of Toronto, Ontario Institute for Studies in Education, 2025)
The aim of my dissertation is to examine the Harassment and Violence (HV) that Latinas face while working in the Ontario Construction Industry (OCI). I was specifically interested in the toxic impact HV has on Latina worker’s professional careers, as well as their personal lives. My qualitative research interviews (pláticas) with fourteen Latina construction workers, provided me with the capacity to explain how the labour they perform, and the legal invisibility by which they are defined, systematically combine to disenfranchise Latinas. I explain how the hyper-visible identity of Latinas on job sites, compounds the invisibility of their labour, even as language barriers significantly diminish their individual capacity to report and combat HV effectively. This dissertation also illuminates the persistent state of vulnerability (harassment, wage theft, and/or working in dangerous conditions) experienced by Latinas working without status in the OCI. I open with a literature review illuminating my uniquely intersectional, methodological position as a Canadian-born, Spanish-speaking academic researcher with more than two decades of experience working as a safety inspector in the OCI. My pláticas with fourteen Latinas working in the OCI reveal how workplace dynamics and regulatory inconsistencies contribute to their vulnerability to supervisory exploitation and discrimination from co-workers. The concepts of tokenism, intersectionality, and the conditionality of precarious status help explain how systemic labour policies have placed women in positions where following workplace regulations can inadvertently reinforce their collective marginalization. I found that the toxic, racialized, gendered culture of the OCI is reproduced even when women receive status, such as in the case of supervisors. I recommend a systemic shift in the culture of the OCI which keeps HV underground and normalizes the approach to Latina women in the industry. My dissertation concludes by recommending that support groups, operating outside of state structures, should be funded to serve as the frontline of protection.

Bridging Education and Career: Post-Secondary Music Performance Curriculum and the Portfolio Practices of Classical Musicians - Richards, Jenna (University of Ottawa, 2025)
This dissertation explores the intersections of music curriculum, identity, and career components to provide a deeper understanding of musicians’ livelihoods in Canada. To assess the alignment of post-secondary training with the practices of professional musicians today, the author studies undergraduate music performance curricula and nontraditional performance work, examines rhetoric surrounding musicians’ identities, and delineates portfolio careers. Drawing on first-hand Canadian data through a national survey and interviews with graduates of post-secondary music performance programs, a survey of adaptive concert performers, and a curriculum analysis based on web-scraped data from five prominent institutions, the dissertation applies social constructionist theory and the transformative lens to emphasize musicians’ perspectives in a practical dissemination of findings. Three core articles address three critical aspects of musicians’ careers: (1) Canadian undergraduate music performance curricula, focusing on coursework beyond core musicianship; (2) the portfolio careers of Canadian-trained classical musicians, assessing employment patterns, career sustainability, training relevancy, and identity formation; and (3) nontraditional performance work, with specific focus on adaptive concerts as an emerging performance avenue. The synthesis and conclusion distill key takeaways and present actionable recommendations for curriculum reform, identity affirmation, and professional preparation. The careers of classical musicians are increasingly precarious and multifaceted, challenging the legitimacy of traditional conservatory models that frame success primarily in terms of full-time performance careers. This research contributes to discourse on music careers by identifying gaps in institutional training and exposing the realities of professional life for performance graduates. By integrating concepts from the performing arts, curriculum, and entrepreneurship, this dissertation offers interdisciplinary insights into how institutions and society might better support musicians in building sustainable careers.

Poverty Policy: Historic Institutional Approaches to Poor Relief in Canada - Robbenhaar, Madeline E. A. (University of Alberta, 2025)
In Canada, social assistance programs act as a ‘safety net’ to prevent those living in poverty from reaching destitution. However, this safety net comes with expectations – in the form of welfare-to-work programs that mandate beneficiaries’ participation in work-related activities. Underlying these welfare-to-work programs are ideas surrounding citizenship, activation, dependency, and the role of the state in supporting the welfare of its citizens. Embedded in these programs are the ideas of market citizenship and activation, two ideas that tell the story of the ideal citizen in Canada: a self-sufficient and appropriately activated market citizen, who fulfils their obligation of supporting themselves through participation in paid employment. Subsequently, through the ideas of market citizenship and activation, social assistance beneficiaries represent the antagonist to the ideal citizen: an unmotivated, dependent, support-needing citizen. Although scholars often situate the emergence of the ideas of market citizenship and activation during the late 20th century period of welfare reform in Canada, this perspective negates the history of these ideas in social assistance policies. Informed by the theory of Critical Human Ecology and the methodology of Ideational Analysis, this thesis explores the development of the ideas of market citizenship and activation across institutional approaches to poor relief in Canada. By taking a long-term historical perspective, this thesis finds evidence of the ideas of market citizenship and activation as early as the 17th century in Canadian institutional approaches to poor relief, and counters the prevailing perspective that market citizenship and activation emerged in the late 20th century in Canadian institutional approaches to poor relief.

The Practice of Intolerance by the Alberta Social Credit Government and the Growth of Jewish Activism Between 1943 and 1968 - Rohfritsch, Jason (University of Ottawa, 2025)
The following thesis paper examines the continued presence of antisemitism in the ruling Alberta Social Credit Party (SCP) between 1943 and 1968, and Canadian Jewish organizational efforts to obtain anti-discrimination legislation. The Alberta Social Credit grassroots movement involved radical monetary policies, religious fundamentalism, conspiracy theories and antisemitic rhetoric. How did such an unorthodox party retain provincial control for thirty-six years despite the organization's persistent antisemitism? The question is significant to the ongoing narrative of Alberta politics amid a sharp rise in antisemitism within Canada today. The principal methodology includes qualitative research of primary sources from the SCP and Canadian Jewish archives and academic literature. Within this study period, the Canadian Jewish Congress (CJC) transitioned from an organization with little infrastructure to a leading institution with strong ties to other Canadian Jewish bodies, and labour and civil groups, struggling to enshrine protections for Canadian Jews. The results demonstrate that in the 1950s and early 1960s, as many Canadian provincial governments enacted equal rights legislation, Premier Ernest Manning's Social Credit government resisted such laws in Alberta. As a result, Jewish leaders escalated initiatives in Alberta. Throughout his leadership, Manning routinely denied accusations of antisemitism leveled against his party. Eventually, Manning and the Alberta SCP government were forced to establish human rights legislation in 1966, although the provisions were limited in scope. Manning curtailed Social Credit antisemitism when it became a political liability, but he did not comprehensively eliminate it. Through collaborative efforts, the CJC and other Canadian Jewish groups finally achieved legalized protections for the Jewish community in Alberta.

Food Insecurity In Canada: Gaining A Better Understanding Of Where And Why It Exists - Russo Spena, Anna (University of Guelph, 2025)
Food insecurity remains a challenge even in high-income countries. This study has two main goals: (i) to explore the factors driving differences in household food security between urban and rural areas; and (ii) to examine public perceptions regarding the existence, causes, and solutions to food insecurity. The first objective is addressed through a multinomial logit analysis of data from the CIS 2021. The second builds on Attribution Theory and involves a survey conducted with a representative Canadian sample, analyzed using factor analysis. Findings show that rural households would be 1.4% more likely to experience food insecurity than urban ones. The identified public antecedents include economic conditions, the food system and government, social support, and individual factors. The government is seen as primarily responsible for addressing the issue. Recommended policy measures include reducing food prices for low-income populations, improving access to affordable food shops, and supporting increased local food production.

Les travailleurs migrants temporaires du secteur de l'entretien ménager dans la région de Québec : Entre précarité, mobilité et agentivité - Tapia, Janelvi Caroline (Université Laval, 2025)
Le contexte de pénurie de main-d'œuvre au Québec lors des dernières années a entraîné une augmentation du recrutement de travailleurs migrants temporaires dans différents secteurs d'emploi. Ces travailleurs sont souvent engagés par des agences de recrutement à l'international ou des agences de placement, particulièrement dans des secteurs considérés précaires et « essentiels ». Hors du secteur de l'entretien ménager, la littérature a montré que les agences façonnent le lien d'emploi des travailleurs avec leur employeur, créant ainsi une main-d'œuvre « flexible », conçue pour répondre aux besoins ponctuels et temporaires des entreprises (Belzile, 2018; Mercure, 2014). Ce mémoire s'intéresse aux travailleurs migrants temporaires du secteur de l'entretien ménager, recrutés par une agence de recrutement à l'international, principalement en hôtellerie, dans la région de Québec. Ce secteur présente une forte variabilité saisonnière des conditions de travail et, par le fait même, est fortement touché par la pénurie de main-d'œuvre puisque de nombreux employés revendiquent précisément cela; de meilleures conditions de travail (Guilbault, 2024). Cette dynamique est particulièrement marquée dans la région de Québec où la nécessité d'embaucher de la main-d'œuvre à l'international est devenue de plus en plus cruciale pour le secteur de l'entretien ménager. Cette étude s'inscrit dans un projet plus large financé par le Conseil de recherches en sciences humaines (CRSH); le projet PARtenariat sur les migrants Temporaires en EMPloi (PARTEMP), qui vise à produire des connaissances sur les travailleurs migrants temporaires dans la région de Québec (Chaire de recherche du Canada sur les dynamiques migratoires mondiales, 2021). L'objectif principal de ce mémoire est de comprendre les expériences et les conditions de travail de ces travailleurs au sein d'un secteur peu exploré dans la littérature en contexte québécois. Les concepts de précarité, de mobilité et d'agentivité sont mobilisés pour appréhender l'expérience des travailleurs migrants temporaires. 14 entretiens semi-dirigés avec des travailleurs de nationalités différentes, majoritairement des latinoaméricains et des femmes, ont été réalisés entre mai et août 2023. L'analyse révèle plusieurs formes de précarité par le croisement de la relation d'emploi, le statut migratoire, le manque d'accès à l'information et la barrière de la langue. La flexibilité, une exigence structurelle du secteur d'emploi, et la mobilité sont des facteurs de précarisation. Le secteur exige des déplacements fréquents verticaux sur le lieu de travail, d'un étage à l'autre, et horizontaux sur le territoire. Cependant, ces travailleurs se montrent créatifs et « résilients », faisant preuve d'agentivité individuelle et collective dans le but d'améliorer leurs conditions de travail et de vie dans la région de Québec.

Deconstructing Human Capital Theory: The Silenced Narratives of Immigrant Women of Colour - Thananayagam, Shanmugapriya Thanuja (University of Toronto, Ontario Institute for Studies in Education, 2025)
This study critically examines the limitations and inadequacies of Human Capital Theory (HCT) in addressing the employment realities of immigrant women of colour in Canada. Rooted in neoliberal ideology and neoclassical economics, HCT assumes that individual investments in education and skills directly lead to economic success. However, this framework fails to account for systemic barriers, structural racism, and gendered discrimination that disproportionately disadvantage equity-deserving communities. Applying Pierre Bourdieu’s concepts of social capital and habitus alongside critical race theory (CRT), this research interrogates HCT to examine how race- and gender-based exclusions, social networks, cultural norms, and institutionalized biases shape career trajectories. While intersectionality is not the central focus, the study integrates an intersectional analysis to highlight the compounded disadvantages faced by immigrant women of colour in the labour market. Employing Indigenous storytelling methodologies and narrative inquiry, this research foregrounds the lived experiences of immigrant women of colour to challenge the assumptions of HCT. By conducting a comprehensive literature review and examining CRT, the study further interrogates how race, power, and systemic exclusion intersect with economic mobility. Despite its widespread acceptance, HCT remains insufficient in explaining the persistent employment gaps and labour market marginalization of immigrant women of colour. This study argues that access to social capital is a critical determinant of career success, often privileging dominant groups while excluding racialized immigrants. The interplay between HCT and social capital theory creates compounded barriers, reinforcing systemic inequalities and limiting career advancement for marginalized populations. As Bourdieu’s work does not explicitly address racial disparities, this study integrates CRT to demonstrate how race fundamentally influences labour market outcomes. By bridging these theoretical perspectives, the research challenges dominant economic narratives and calls for policy reforms that recognize and dismantle structural barriers to economic equity for immigrant women of colour.

Resource Rhetoric in Three Canadian Novels, 1919-1945 - Uher, Valerie (University of Waterloo, 2025)
In this dissertation, I propose the term resource rhetoric to describe the cultural logic that renders extractivism an interminable part of Canadian identity. As Canada solidified its settler-colonial expansion in the nineteenth and early twentieth century, there was an attendant formalization of infrastructures promoting the extractivist ambitions of the state. Within those infrastructures a resource discourse—of natural resources and human resource management—was born. In Resource Rhetoric in Three Canadian Novels, 1919-1945, I examine three novels that articulate a cultural dimension to Canada’s broad attempt to adapt workers to a confluence of precarious working conditions in the first half of the twentieth century. I analyze the downplaying of class formation in these novels and link it to their use of resource rhetoric—tropes and figures that assert the primacy of the extractivist state over and against the primacy of the working-class collective. My thesis develops by first establishing the 1919-1945 period as one marked by an unease about whether workers could truly become the “human resources” Canada’s extractivist economy needed. I explore how this uncertainty is manifested in Douglas Durkin’s 1923 novel The Magpie, an economic novel set during the 1919 Winnipeg General Strike. I then demonstrate that during the interwar period, a worker’s success in embodying the ideal Canadian “human resource” identity was measured against a racial hierarchy emerging from eugenic ideology. In my analysis of Irene Baird’s 1938 novel Waste Heritage, I consider how the “rank and sort” logic of eugenics is used to calibrate moral rectitude in the novel’s portrayal of labour strife among Canada’s Depression-era unemployed. In the second part of my thesis, I consider how human resource discourse expanded to include social reproductive labour in the period just prior to the establishment of Canada’s welfare state. I argue that Gabrielle Roy’s 1945 novel The Tin Flute makes the home a terrain for potential class struggle against the exploitation of women’s work, while at the same time positioning this work as vital for the Canadian state to function. The rhetorical framing of workers in these novels consistently emphasizes their lack of agency and cooperation; foregrounds their interchangeability, and stresses workers’ inability to overcome their circumstances because of these factors. They articulate a deep-seated clash between the imperative that workers act as assets to Canada’s resource state, and the imperative that they might improve their lives through class formation and solidarity. While these novels are generally aligned with the resource discourse of the era, they demonstrate one fundamental failure of extractivist ideologies and resource logic: a person can never truly be a “dematerialized asset,” or a “universal Canadian worker subject.” My main claim in this thesis is that these novels show that to be a human resource is an unattainable goal.

Dependent Contractors and the Ontario Labour Relations Board: Understanding the Board's Role in a Capitalist Economy - Walchuk, Bradley Peter (York University, 2025)
This dissertation explores the evolution and politics behind the concept of the ‘dependent contractor’ in Ontario, from its earliest incarnations in the late 1970s to its current usage in the gig economy, as interpreted and applied by the Ontario Labour Relations Board (OLRB). It examines how the Board’s interpretation and application of dependent contractor provisions has impacted workers whose employment status falls somewhere between traditional notions of independent contractor and employee, i.e. the ‘grey area’ as the Board has referred to it, over a period of changing employment relationships and of increasingly precarious work. The research tracks these changes over time, examining how previous OLRB jurisprudence on dependent contractors can be seen to impact its decisions in more contemporary contexts (e.g Foodora, 2020) and what this might tell us about the Board’s understanding of employment relations in a changing capitalist economy. The analysis seeks to place the actions of the OLRB into a broader social context to assess what factors have influenced the Board’s decisions and gauge how it understands both its potential to address employment inequities and the limits it faces in doing so within a capitalist economy. This dissertation argues that the OLRB operated with an implicit industrial pluralist understanding of labour-capital relations and made decisions informed by that approach and, in doing so, lacked an appreciation of how capitalist workplaces were changing over time in a way that evaded control via that understanding. It further argues that while bodies such as the OLRB have some autonomy from capitalists and the capitalist state, they are unable to, nor are they designed to, overcome or dramatically alter the power imbalances that exist in capitalist civil society.

Empowered Margins: Women, Work, and Justice in Educational Labor - Woodford, Erin (Antioch University, 2025)
This dissertation examines economic justice and employment precarity faced by educators in both K-12 and post-secondary education systems. While literature explores themes of changing demographics in union membership, collective bargaining, labor activism, and gendered and intersectional inequities in academia, and women in leadership in unions, a critical gap of disabled women’s voices and solutions to the inequities remains. This study highlights how job insecurity, unequal pay, hiring biases, limited recognition of prior learning, and inadequate institutional support exacerbates mental health challenges, professional invisibility, and economic instability. In the K-12 unionized system, systemic barriers such include disregard for substitute teaching as a viable career and challenges for experienced teachers to get hired over cheaper, inexperienced teachers. In post-secondary education, shifting immigration policies, funding cuts, and undervaluation of non-traditional scholarship deepen instability. This research advances equity-focused strategies. By integrating lived experience with structural and systemic critique, the study calls for reforms that prioritize stability, recognition, and inclusive pathways for all educators navigating precarious employment and economic justice. The study contributes to broader conversations on improving women’s engagement and addressing the inequalities inherent in current labor systems.

Ethical Procurement In The 2026 FIFA Men's World Cup: Toronto's Efforts In Combating Sweatshop Labour - Al Horoub, Yazan (York University, 2024)
The anti-sweatshop movement has long committed to abolishing sweatshop labour and ensuring workers’ rights for all. There is an established body of literature on sport and the anti-sweatshop movement on the roles played by a range of actors concerning the mega-sporting events, which have been plagued with abuses of workers’ lives in the name of the sport spectacle. In effort to move past this troubled history, FIFA has embedded internationally recognized human and labour rights into their 2026 bid process. This study evaluates how the City of Toronto, Canada Soccer Association, and FIFA have considered ethical procurement and sweatshop labour as part of their bid for co-hosting the 2026 FIFA Men’s World Cup. Employing a critical theoretical approach, this study finds that despite the varying levels of considerations given to ethical (anti-sweatshop) procurement, the efforts remain insufficient. This is attributed to the unequal power dynamics that prioritize a discourse of (neoliberal capitalist) development for soft power.

Stigmatized (M)Others: Navigating Stigma, Sex Work, and Motherhood in Canada - Annett, Michelle Lesley (Carleton University, 2024)
Despite a large body of research exploring the obstacles sex workers face due to their occupational stigma, little research focuses on how their stigmatized paid work influences their navigation of unpaid care, especially in the context of the COVID-19 pandemic. My dissertation examines the narrated and photographic experiences of womxn in Canada who identify as both mothers and sex workers and asks: how do these womxn navigate and negotiate the daily work of unwaged social reproduction and paid work in stigmatized and precarious conditions? This dissertation is informed by feminist methodologies, visual methodologies, and contributes to literatures on stigma, sex work stigma, social reproduction, unpaid care work, mothering, and working motherhood. Fourteen participants in this qualitative project engaged in autophotography, capturing their daily routines and surroundings to provide visual insight into their daily lives. Then each participant attended a photo elicitation interview to discuss the meanings, experiences, and feelings being conveyed in their selected photographs. My findings illuminate that sex work stigma operates contextually, influencing these mothers’ engagement with and disclosure of their stigmatized paid work, their families’ experiences with courtesy stigma, and the structural barriers they face as sex working mothers. This dissertation also explores participants’ engagement with mothering practices, crediting their ability to be good, empathetic mothers because of their experiences navigating stigmatic occupations and their transferrable skills as sex workers. Womxn’s choices to navigate sex work and mothering are acknowledged as being both calculated and meaningful— granting sex workers financial security, flexible working hours, and unique opportunities to invest time into themselves and their families. To uphold the aims of producing accessible research, these images were displayed in public fundraising exhibits, relying on participant observation and anonymous feedback to further assess the project’s ability to co-produce destigmatizing and empathetic knowledges—by, with and for sex workers. All funds raised from these exhibits were donated to various sex worker grassroots organizations in Canada to assist in funding their ongoing mutual aid efforts and to ensure this research possess tangible benefits for sex workers themselves.

Platform Labour, Migration, And Resistance: Organizing Against Hyper-Exploitation In Paris And Toronto's Food Delivery Industries - Baril, Emile (York University, 2024)
This doctoral thesis combines empirical research and theoretical innovations aimed at comprehending the dynamics of platform labour within advanced-capitalist economies. Through case studies in Paris, France, and Toronto, Canada, the thesis contributes to the evolving landscape of platform labour studies, migration studies, and labour geography. The over-representation of racialized immigrants engaged in platform food delivery has attracted significant attention from both academia and mainstream media, notably in Toronto with international students from India and in Paris with sans-papiers from Africa. Focusing specifically on migration and working conditions, this study unveils hyper-precarity in Euro-American cities. The primary objective of the thesis is to provide a new perspective that includes immigration and citizenship within current discourse on platform labour. Drawing inspiration from critical urban studies, migration studies, and science and technology studies, the research introduces two conceptual propositions: i) “citizen-rentier-ship”, designed to elucidate how various stakeholders benefit from precarious citizenship status, and ii) a “relational comparison” of platform labour resistance, offering insights into the evolution of the unrest against platform labour exploitation—a crucial facet of urban development. The thesis is based on extensive interviews with food riders, workers, spokespersons, and other key actors, shedding light on their capacity for self-organization within advanced capitalist societies. By exploring strategies, limitations, and the dimensions of resistance—both digital and physical—through interactions with riders and individuals who resisted deactivation, low wages, and algorithmic management, the research contributes to a nuanced understanding of the challenges and opportunities faced by these workers. The case studies place emphasis on migrant workers’ perspectives. They reshape ongoing debates about global platforms by centering attention on the bottom ends of labour markets. In conclusion, the study contends that the struggles of migrant workers are deeply entwined with labour laws, immigration policies, misclassification practices, and urban policies in France and Canada.

Working-Class Affects: Connecting Affect Theory to Trade Union Revitalization Efforts - Barnett, Bronwen (Simon Fraser University, 2024)
In recent years, labour unrest in Canada and elsewhere has led to a resurgence in union organizing, job action and contract gains. This thesis sets out to understand how greater attentiveness to working-class affects or emotions might support this potentially revitalizing moment. Given the limited scholarship in this area, this study connects a literature review of affect theory with radical labour history to develop a framework for thinking about the affective dimensions of collective action within unions. Using that framework, the study then investigates the affective life of two Western Canadian unions through surveys and interviews. The thesis concludes that acknowledging and becoming more intentional in efforts to mediate the affective intensities that circulate, move people and organize life at the level of union membership represents an important focal point as a new cycle of class recomposition potentially takes shape.

Advocating for Labour Mobility and Permanent Residency for Canada's Seasonal Agricultural Workers from an International Human Rights Law Perspective - Barzegarikhanghah, Lily (Faezeh) (University of Manitoba, Faculty of Law, 2024)
This paper delves into the implications of Canada's Seasonal Agricultural Worker Program (SAWP) through the lens of international human rights law (IHRL), spotlighting the nuanced effects on migrant agricultural workers' rights. Originating in 1966, the SAWP has been pivotal in recruiting labour from Mexico and the Caribbean to bolster Canada's agricultural sector. The paper critiques the program's core policies, notably the restrictive employment system that ties workers to specific employers and the significant barriers to obtaining permanent residency (PR) and citizenship. These policies are scrutinized for their potential violation of fundamental human rights, including the rights to equality, liberty and security, and access to justice, under both Canadian and international legal frameworks. A comprehensive analysis is presented, underpinning Canada's obligations under IHRL and the apparent discrepancies within its treatment of SAWP participants. The study proposes substantial policy reforms aimed at rectifying these discrepancies, advocating for a transition towards open work permits, and establishing clear pathways to PR and citizenship for SAWP workers. The research underscores the necessity for Canada to reconcile its labour demands within the agricultural sector with its human rights obligations, ensuring a fair and humane treatment of migrant workers who play a crucial role in the country's economy.

Tell Dem Wagwan Fanon: On [Colonial] Violence and Prison Labour in Canada - Batelaan, Krystal Alisha (York University, 2024)
In this dissertation, I draw on Frantz Fanon’s concepts of cultural imposition and collective catharsis to examine how the colonized subject, like the incarcerated Black worker, undergoes a double process of dehumanization wherein they are perceived as both an invisible and hypervisible subject. I argue that the colonized subject is invisible insofar as they are subjected to various forms of dehumanization such as physiological and psychological abuse, lack of access to resources, and neglect. However, they are also perceived as hypervisible because they are viewed as existing in excess as hypersexual, hyper deviant, and hyper criminal creatures and therefore deserving of the treatment they endure. Similarly, the incarcerated worker is viewed as invisible and hypervisible because they are viewed as unskilled and subhuman beings undeserving of adequate pay and protections but are also perceived as best suited to work in poor conditions doing less skilled, undervalued, low-paying work. By tracing how this relationship between race, racialization and labour is underpinned by whiteness both historically and in a contemporary sense, I demonstrate how the use of prison labour within a Canadian multicultural context must necessarily be read through a normalizing white gaze, under the guise of public safety and rehabilitation; here the prison functions as a disciplinary site wherein Black and racialized prisoners are constructed as inferior beings in need of heightened control through labour. In doing so, I argue that the use of prison labour in Canadian prisons is a form of colonial violence that reproduces inferior and superior colonial identities.

Policing Sex Work Online: Sex Workers’ Views on the Risks and Benefits of Using AI to Police Online Ads for Sexual Services - Brown, Sydney (Simon Fraser University, 2024)
This thesis explored the potential use of artificial intelligence (AI)-based policing models in law enforcement anti-trafficking initiatives and examined potential impacts of expanding state surveillance through police use of AI-based policing models. Computer scientists aspire to develop AI to identify victims of trafficking through websites that host ads for sexual services. Little research has explored sex workers’ views on the proposed AI-based policing models and their likely impacts. To fill this gap, I conducted 21 semistructured interviews with sex workers, academics, and members of sex worker rights organizations to discuss the effects of AI-based policing models. Participants expressed concern that these models will continue a long history of anti-trafficking initiatives causing harm, particularly against racialized, migrant, and transgender sex workers. Findings also suggest developers should be cautious about creating AI-based policing models without input of sex workers and without a firm knowledge base of the sex industry.

Masculinity and Gig Work: A Case Study of Rideshare Workers in Toronto - Campo, Maya Selina (York University, 2024)
This thesis examines shifting masculinities and platform labour, following eleven semi-structured interviews conducted with male Toronto-based Uber and Lyft rideshare workers with dependents (children). Women have commonly done non-standard work, hence the proliferation of non-standard work being contextualized as the ‘feminization of work’ (Zahn, 2019). In contrast, rideshare work is a non-standard form of gig work done predominantly by men, rendering it a relevant form of platform work to examine with its complicated relationship to the historical context of gender and nonstandard work. This thesis argues for a need to organize the worker as a whole, examining how workers’ unpaid social reproductive labour and balancing of rideshare work, and often another form of paid work, impacts the viability of classic organizing methods. I argue that these issues of convoluted boundaries between paid and unpaid work must be incorporated into the potential organizing demands of a rideshare workers’ union and identify areas for further research on organizing rideshare workers accounting for shifting masculinities.

Disposable Qualifications, Disposable Lives: Examining the Labour Market Experiences of Foreign-Educated Racialized Immigrant Women - Chinchamie, Lisa (University of Toronto, Ontario Institute for Studies in Education, 2024)
This qualitative research study examines how the Labour Market Integration (LMI) site constitutes a site of ongoing colonial violence and spirit injury, where race plays a central role in legitimizing the politics of credential recognition, in which Foreign Educated Racialized Immigrant Women (FERIW) are evicted from the category “qualified” in Canada. My analysis draws upon concepts of racial capitalism and structural violence to locate the acts of eviction that FERIW are subjected to within the LMI space in Canada and the consequences and impacts of this eviction. I argue that racialized immigration on the move to Canada represents the human face of Canada’s ongoing nation-building and economic policy agenda. The LMI space reinforces and reproduces the colonial racial hierarchical order in Canada. Based on qualitative interviews with 12 FERIW, I explore how within the LMI space, racialized immigrant women are stripped of their foreign credentials, discursively framed as unqualified and deficient, and repurposed as a source of cheap labour within the political economy. Delegitimization carries severe material and socio-economic consequences. The intersectionality of race, ethnicity, gender, class, and immigrant status results in FERIW becoming “ghettoized” into low-paying, precarious, low-end jobs, and, for many of these women, low income and poverty. This work represents a decolonial work articulated through anti-colonial and feminist anti-racist theory, to present a nuanced historical account of the experiences of gendered racialized immigrant labour within global and local structures that look very similar to the old structures of colonialism.

Queer Oral Histories of Deindustrializing Cape Breton - Devitt, Liam (Concordia University, 2024)
Queer history in Canada has often centred around metropolitan areas, like Toronto and Montreal, usually foregrounding social movements. This means that queer histories of the periphery are often overlooked, and that histories of metropole are taken as representative of the national context. In this thesis, I examine queer oral histories of Cape Breton, Nova Scotia. Through these oral histories I aim to complicate dominant narratives in both queer history and histories of deindustrialization in Canada. Cape Breton is a former steel and coal region in Nova Scotia that underwent a comparatively slow, state-managed deindustrialization in the latter half of the 20th century. Today, like in deindustrialized areas across the world, the “structure of feeling” of industrial life remains, despite plant and mine closure. Often, histories of deindustrialization center around a mythologized white male (and indubitably heterosexual) breadwinner, centering not just workers, but the specific function that masculine industrial labour played in the social reproduction of the Fordist accord in the household. By taking up the life stories of queer people, we can critically examine this centring of the nuclear family in deindustrialization studies. In the first chapter, I offer a theoretical and historiographical intervention arguing for a queer investigation of deindustrialization. In the second chapter, I apply this line of thinking to oral histories of Cape Breton queers, arguing that these narrators’ desires for queer history and queer future are ultimately filtered through the prism of deindustrialization’s half-life.

The Making of Blindness in Ontario: Incarceration and Class Formation, 1872–1926 - Dressler, Harrison (Queen's University, 2024)
This thesis examines the experiences of pupils-cum-inmates who attended the Ontario Institution for the Education of the Blind (OIB) during the late nineteenth and early twentieth centuries. Customary assessments of segregated education, which investigate administrators’ campaigns to implement pedagogical or curricular advancements, have characterized institutionalization as educational and emancipatory. Instead, this project challenges identity-centric, rights-based narratives by reframing the OIB as constitutive of Ontario’s carceral apparatus. Drawing upon first-person testimony gathered during four investigations into the OIB conducted by the Government of Ontario, the analysis demonstrates that capitalist development dispossessed blind Canadians from waged labour, generating an underclass of precarious and oft-wageless proletarians. Institutionalization socialized the workers-in-training within a prison-like environment where punishments like whippings and beatings, solitary confinement, and material deprivation were commonplace. Educational opportunities were haphazard and irregular, while living and working conditions were uncomfortable, bordering on intolerable. Biomedical understandings of blindness rationalized the mistreatment of inmates, as administrators attempted to reintegrate graduates into waged labour. Children and adolescents survived by developing cultures of delinquency and transgression; inmates, especially working-class inmates, organized popular resistance movements that challenged institutional authority. Educational authorities responded by overseeing the repression of working-class culture. By funneling graduates into either working-class occupations or “gentlemanly” and “learned” professions, institutionalization fomented processes of class formation, creating, first, an underclass of labourers and musicians and, second, a vanguard of capitalists and professionals.

Maritime Mastery: An Appendage of the West Indian Plantation and New England in Colonial Canada - Eaton, Jesse R. (University of Calgary`, 2024)
Scholarship on the development of slavery in the colonial Maritimes region during the pre-Loyalist period remains scarce, with even fewer studies examining slave ownership. By situating the expansion of slaveholding in the region (that makes up present-day Nova Scotia, New Brunswick, and Prince Edward Island) within the Atlantic world socio-economic context, I show how Maritime society reproduced anti-Black attitudes and slaving practices found in West Indian slave societies. Through trading and social relationships with New Englanders, the region’s colonisation became tethered to the Caribbean. New England’s commercial dependence on West Indian plantations beginning in 1637, and expanding thereafter, fostered intra-regional mercantile and military ventures, bringing their Caribbean partnerships into the Maritimes after the Treaty of Utrecht in 1713. The social aspects of these commercial interactions reveal how settling New Englanders transplanted their ideological, interpersonal, and familial connections to the Caribbean and their slaveholding norms to the Maritimes. By comparing Maritime slave-owning practices to those found in the West Indies, we see Maritime slaveholding to be, in many ways, a mere extension of the plantation regime.

The Confederation of Canadian Unions (CCU), 1969-1992 - Godden, Mason (McMaster University, 2024)
This dissertation provides the first historical overview of the Confederation of Canadian Unions (CCU) and its affiliates from 1969 to 1992. Formed at the end of the 1960s as a foil to the Canadian Labour Congress (CLC), the CCU sought to nationalize the Canadian labour movement by fomenting the formation of Canadian unions. As a left-nationalist labour body, the CCU charged the CLC with conservatism, complacency, and collaboration in its approach to organizing and collective bargaining. Chief among the CCU’s concerns was the domination of American international unions in the CLC. Throughout the 1970s and 1980s, the CCU organized workplaces in unorganized industries, bringing a host of immigrant women into the ranks of the Canadian labour movement, while establishing large bargaining units in industries primarily organized by American unions. At the same time, the CCU forwarded a left-nationalist politics inspired by the New Canadian Political Economy (NCPE) that criticized Canada’s economic, political, and cultural dependence on the United States, and used this politics to mobilize its members against continental free trade and towards a nationalized, socialized home economy. The CCU and its affiliates also formed important linkages with the New Left and the women’s movement during these decades and proved itself a militant actor in confrontations with the state and industrial law. Several CCU affiliates eventually merged with the Canadian Autoworkers (CAW) in the 1990s in the wake of extensive economic restructuring and corresponding changes in the Canadian labour movement. The dissertation contributes to the scholarship on industrial relations, industrial legality, and nationalism by providing a historical case study of a left-nationalist labour institution that simultaneously challenged and was shaped by federal and provincial law. It provides a critical institutionalist perspective on union federations that accounts for the law as a contested terrain, and nationalism as a historically contingent politics.

Not All Disability Is Created Equal: A Comparative Historiography of Workers' Compensation and Disability Benefits in Ontario, Canada - Heath, Bonita Lee (York University, 2024)
This dissertation establishes that work injury and injured workers are relatively neglected in Critical Disability Studies (CDS). A further observation is that CDS tends to avoid a class analysis of disability politics in favour of identitarian approaches. This research focuses on income security. Through a Marxist critical policy historiography, I compare workers’ compensation benefits and state-sponsored benefits for disabled people whose disabilities originated outside of the workplace in Ontario. I argue that the workers’ compensation program is superior to the state-sponsored program because of the class location and politics of the respective groups of people with disabilities seeking income security. The discussion also highlights some of the reasons for the missing injured worker in CDS. Specifically, injured workers experience disability as a loss worthy of compensation rather than a positive identity. Further, rather than viewing prevention measures as the erasure of disabled people, injured workers support the prevention of disability through occupational health and safety laws and workplace practices. By focusing on the political economy of each program, the historical narrative suggests that disability benefit programs in Ontario were developed less by moral suasion and more because of their role in capital accumulation. Although the argument holds for the early history of the two programs in their early history. the negative impact of neoliberalism on both workers’ compensation and the current benefits program in Ontario (the Ontario Disability Support Program) has created a convergence of interests between permanently impaired injured workers and other disabled people, underscoring the importance of including injured workers’ perspectives in CDS.

Experimental Regulation to Address Modern Slavery and Forced Labour in Global Supply Chains: Canada's Passage of Transparency Modern Slavery Legislation - Humphrey, Jonelle (McMaster University, 2024)
Embargoed until: 2025-11-29 This thesis explores Canada’s regulatory response to modern slavery in global supply chains. It investigates the factors which influenced Canada to enact transparency modern slavery legislation. It also analyzes Canada’s strategy of utilizing multiple soft and hard law governance and regulatory techniques to strengthen its response to modern slavery. Using a theoretical framework which combines global governance and regulation literature with literature regarding the national institutionalization of global norms, this thesis examines how international actors that comprise the global anti-slavery network disseminate anti-slavery and corporate accountability norms. These norms are subsequently filtered through a country’s domestic political economy, and are translated into either transparency or mandatory human rights due diligence (MHRDD) legislation. The qualitative methods used in this thesis were documentary analysis and key informant interviews. Key informant interviews in conjunction with an analysis of relevant reports and parliamentary debates provided insight into the influences behind Canada’s enactment of various governance and regulatory techniques. Doctrinal legal analysis, and an assessment of the various techniques implemented in Canada, revealed the effectiveness of the individual techniques and how they interacted with each other. This thesis found that Canada adopted a transparency law due to a combination of: (1) International norm diffusion via an epistemic, global anti-slavery network; and (2) Canada’s unique domestic political economy. Features of Canada’s domestic political economy, including its affiliation as part of the Anglosphere, and its powerful mining industry, ultimately determined the enactment of transparency legislation. The thesis also found that Canada’s use of multiple, increasingly hard law governance and regulatory techniques is currently ineffective as these techniques do not complement each other, and actually weaken Canada’s regulatory response to modern slavery. Consequently, labour standards have not improved for supply chain workers. This thesis posits that Canada should prioritize centering and empowering workers to protect their own rights.

The Effects of Minimum Wage Increases on Employment and Average Wages of Affected Workers in Canada - Iray Makvandi, Alaleh (Concordia University, 2024)
The employment effects of the minimum wage are debated among economists, with traditional competitive models suggesting potential job losses for low-wage workers, while alternative models like institutional and dynamic monopsony suggest potential positive impacts. The institutional model posits that raising the minimum wage could boost employment if wages are below the marginal product of labor, and the dynamic monopsony model suggests that higher minimum wages could reduce turnover costs in low-wage labor markets, mitigating predicted job losses. Empirical studies, even within the competitive model, show mixed results, with some indicating significant disemployment effects and others not. This thesis provides a comprehensive analysis of the impacts of minimum wage increases on employment and wages across Canada, utilizing a robust methodological framework including the bunching approach, event study analysis, and difference-in-difference methods to examine the effects of varying provincial minimum wages over time.To accomplish this, I first employ the bunching approach to detect any concentration of wages just above the minimum wage threshold, providing insights into employer behavior in response to wage regulations. This technique identifies subtle adjustments in wage distribution that might not be apparent through other methods. Next, I utilize event study analysis to explore the immediate and long-term effects of minimum wage hikes, comparing employment and wage data from periods before and after the increases. This method captures both short-term disruptions and long-term adjustments in the labor market. Additionally, the difference-in-difference method is employed to compare outcomes between provinces with and without minimum wage increases, isolating the specific effects of these policies by controlling for other influencing variables. This approach underscores the importance of regional economic conditions in shaping the effectiveness of wage regulations. The empirical analysis begins with Labor Force Survey data from Ontario, which experienced significant real minimum wage increases in January 2018. The study estimates the counterfactual frequency distribution of hourly wages in Ontario for three years before and two years after the minimum wage increase. The findings show a significant decrease in jobs paying below the new minimum wage and a proportional increase in jobs paying up to $4 above the real minimum wage, indicating no significant overall employment impact. Contrary to anticipated employment effects, the average wage of affected workers increased significantly by 22.7% over the two years following the minimum wage shock. The only exception in the Ontario study was for the teen group; contrary to much of the existing Canadian literature such as Fossati and Marchand (2024), I found a significant positive employment effect for teenagers. However, overall, I did not observe a significant negative employment effect for young adults. Further analysis includes other provinces, such as Alberta, and cities such as Gatineau versus Ottawa, which also experienced substantial nominal and real minimum wage increases. The study applies the same methodology to assess the employment and wage effects, finding similar results to the Ontario study. Contrary to the Ontario study, in the Alberta study, I found a significant negative employment effect for the teen group, but overall, I did not find a significant negative employment effect for young adults. Since referring to a single minimum wage is inherently problematic, I also investigated a pooled analysis of hourly wage data from all Canadian provinces from 1999 to 2019. This analysis, covering 56 minimum wage increases, reveals no significant employment effect (-2%) over six months following minimum wage increases but a significant average wage increase (6.4%) for affected workers. The study also investigates potential employment shifts from low-skilled to high-skilled workers, finding no indication of such shifts. Subgroup analyses by education level, age, and other demographics show approximately similar employment and wage effects, suggesting that the consequences of minimum wage policies are shared among different worker groups. Additionally, sectoral analyses show no negative employment effect in the food industry, aligning with Card and Krueger (1993)’s findings on the impact of minimum wage increases in the fast-food industry. However, a significant negative employment effect (-4%) was observed in the retail sector, highlighting the influence of local industry composition on minimum wage impacts. Finally, in the Canada study (pooling all 56 minimum wage increase across all provinces), I assess the size of wage spillovers, finding that only 7% of the impact on average wages of affected workers comes from wage spillovers at the lower part of the wage distribution, which was statistically insignificant. This aligns with Canadian literature, such as Campolieti (2015), which found modest wage spillovers based on Canadian data compared to American data. Overall, this thesis provides robust evidence on the employment and wage effects of minimum wage increases in Canada. The findings suggest that, contrary to the traditional competitive model, minimum wage increases do not significantly reduce overall employment of low-wage workers and can lead to substantial wage gains for them. This has important implications for policymakers considering minimum wage adjustments to improve labor market outcomes for low-wage workers.

Workers in Canada's Energy Future: Sociotechnical Imaginaries, Settler-Colonialism, and the Coastal Gaslink Pipeline - Lajoie O'Malley, Alana (University of Ottawa, 2024)
In recent years, scholars of science and technology studies (STS) have increasingly turned their attention to the role of collective imagination in shaping sociotechnical futures. This scholarship leaves open the question of how the collectives involved in bringing these futures to life come into being. Starting with one episode in the ongoing conflict over the construction of Coastal GasLink pipeline on Wet’suwet’en territory in settler-colonial Canada, this discourse analysis draws on scholarship in feminist, anticolonial, and co-productionist STS to study this process of collective formation in relation to sociotechnical futures. It does so by examining how oil and gas workers become enrolled into a sociotechnical imaginary I call Canadian resource techno-nationalism. Comparing media and politicians’ representations of oil and gas workers with White workers’ representations of themselves indicates that they can end up participating in this imaginary regardless of their affinity to it. Examining policy documents and scholarly literature about the inclusion of Indigenous knowledges in impact assessment, as well as political debates and mainstream media coverage about the conflict over the Coastal GasLink pipeline, draws attention to how elites’ active construction and protection of the boundary between knowledge and politics works to enroll Indigenous people into oil and gas jobs and, therefore, into the collective performing Canadian resource techno-nationalism. In both cases, elite actors deploy the resources at their disposal in ways that help funnel oil and gas workers into lives imagined for them, securing the power of the settler state in the process. This dynamic illustrates the importance of disentangling participation in the collective performance of sociotechnical imaginaries from freely given consent. Residents of liberal states can end up performing dominant imaginaries less out of any sense of affinity to them than as a response to the disciplinary power these imaginaries help sustain.

Smoke on the Water: A Critical Discourse Analysis of Reconciliation in the Case of the Mi’kmaq Moderate Livelihood Fisheries - MacCarthy, Liam (Dalhousie University, 2024)
Indigenous communities have been in direct conflict with the Canadian state when asserting their right to self-determination. Literature reveals that the Canadian state interprets Indigenous resistance as a threat to settler authority, responding with violence and criminal enforcement. This thesis investigates the relationship between the norms related to Indigenous rights articulated in the Truth and Reconciliation Commission and the institutional enforcement response to Indigenous resistance in the case of Mi’kmaw moderate livelihood fishing. Through a critical discourse analysis of Fisheries and Oceans Canada and Royal Canadian Mounted Police’s public statements, policy documents, and recorded actions, this research found a discursive influence on state institutions. Despite the rhetorical commitments, this research found that state response continued an approach of criminalization and violence against Mi’kmaw moderate livelihood fishers. These contradictions between rhetoric and practice challenge the institutional legitimacy of settler authority.

Ableism in Higher Education: Collective Agreements, EDI [Electronic Data Interchange] Initiatives, and Accommodation Policies - McCabe, Kealin M. (University of British Columbia, 2024)
This study explores ableism within higher education through an examination of the collective agreements and institutional policies that govern the academic responsibilities of disabled faculty members. Critical disability theory serves as the theoretical framework for this study, which employs both institutional ethnography and qualitative content analysis in the review of the publicly available documents from English speaking U15 Group of Canadian Research Universities (n=13). The study unfolds in three parts: Part I presents the findings from the analysis of the collective agreements and institutional policies outlining the tenure and promotion process and the barriers disabled faculty members experience in fulfilling their academic responsibilities. Part II explores the tensions and contradictions between institutional accommodation processes and the language used in their public presentation of EDI initiatives, while Part III represents the everyday experiences of disabled faculty members though interviews, representing the embodiment and internalization of the texts examined in parts I and II. This research challenges and disrupts normative understandings of what it means to be a “good academic”, by addressing an absence in the literature exploring ableist representations and assumptions present in collective agreements and institutional policies. The examination of these texts and the lived experiences of disabled faculty members through interviews has illuminated the existing contradictions and tensions in these texts, showing ableism is strongly entrenched and condoned in university policies and governance.

"His Toolbox is not Full": Unpacking Worker Experiences and Addressing Labour Support in Atlantic Canadian Fishing - McTaggart, Benjamin (University of Ottawa, 2024)
Given the importance of the fishing industry to the Newfoundland economy and identity, understanding the realities of fish work in the province allows for a deeper understanding of labour practices, safety regulations, and the health of the many fisheries the bolster that Newfoundland economy and identity. Initially designed to assess the working experiences of migrant workers on Canadian fishing boats, this thesis turns to domestic workers to unpack labour realties and address the potential of exploitative and abusive practices that help chart fishing among one of the most dangerous jobs in the world. This research took place in Newfoundland in October of 2022, where crew members, boat captains, their owners, and industry and union representatives were approached to gather work experiences and opinions on the broader regional fishing industry in the province. From these experiences, an assessment of how and if exploitative working conditions can be improved utilizes existing and proposed international labour conventions, understandings of unionization, and the political economy, to represent exploitative labour conditions along a continuum. The evolving and changing economic and environmental realities of fishing both globally and in eastern Canada highlight how an already risk-taking, masculine, and community focused industry lives with, is shaped by, and can work towards limiting, the more damaging forms of exploitation. This thesis utilizes qualitative data to inform its assessment of precarious labour realities at sea in the Newfoundland fishing industry to further advocate for the move towards regionalized and industry specific seafarer support mechanisms. Through promoting these mechanisms, such as a seafarer support centre and the ratification of the Work in Fishing Convention (C188), this research calls for Newfoundland's fishing industry to lead the way towards better practices nationally.

Learners or Earners? Interviews with International Students in Canada on Navigating Student-Worker Mobility Pathways - Merriam, Deanna (University of New Brunswick, 2024)
This thesis explores the lived experiences of international students in Canada, examining the impacts and outcomes of Canada’s International Student Program (ISP) that positions students as not only educational participants but also flexible economic assets. Through a brief review of international student policy developments, it is argued that these changes reflect a deliberate effort to commodify international students' labor to meet Canadian labor market demands. The thesis also draws on migration literature to highlight the exploitative risks inherent in foreign labor pathways, applying these concerns to the International Student Program. Through the use of qualitative semi-structured interviews with international students and support professionals, this study reveals the challenges students face under these policies including permit or program navigation, financial instability, and most notably adverse impacts on well-being. This study highlights the complex relationship between Canada’s various mobility programs and notes the benefits of utilizing qualitative methodologies in researching program outcomes.

An Unexpected Alliance: A Participatory Case Study of Labour-Environmentalist Collaboration for Better Transit in the Central Okanagan - Pulles, Kirstin (University of British Columbia, 2024)
This thesis investigates the role of Kelowna’s public transit union (the Amalgamated Transit Union Local 1722 – ATU 1722) and a youth-led environmental group (Fridays for Future Kelowna) in the formation of the Okanagan Transit Alliance (OTA). The OTA is a grassroots movement for better public transit in the Central Okanagan. The central research question is, "how can transit unions engage in climate activism?". A participatory activist methodology is employed to study the joint campaign for more accessible, publicly managed, and community-driven transit. The findings are organized into three themes. The first theme is ecosocialism – a political ideology which centers ecological concerns in socialist thought – because the campaign advocates for an ecosocialist goal of ending the private management of Kelowna’s transit. The findings in this area highlight the importance of organizing around people’s basic needs, uncertainty about the role of the government in the campaign, and that engaging in collective struggle is important for developing working-class power. The campaign was co-led by the ATU 1722, and so the second theme, unions, examines their role in the campaign. Under this theme are the findings that the two leading organizations developed a mutually beneficial collaboration, and that the public facing role of bus drivers helped the union build connections with the community. At the same time, contemporary union challenges impacted the ATU 1722’s ability to engage in effective advocacy. Finally, under the third theme of organizing, the research broadly explores organizing tactics to develop the climate justice movement. We found that a welcoming environment and co-creation led to high participation levels, and that relationships were fundamental to the campaign. This thesis highlights the potential of unions to play a pivotal role in climate activism, bridging the gap between labor and environmental concerns. The case of ATU 1722, Fridays for Future Kelowna, and the OTA serves as an inspiring example of how labor organizations can actively contribute to the broader movement for environmental justice and ecosocialist transformation. This study not only informs the ongoing discourse on the intersection of labor and climate activism but also inspires future collaborations for anti-capitalist climate justice.

Labour Market Gatekeepers: The Role of Human Resource Management Professionals in Immigrant Labour Market Integration in Alberta, Canada. - Redwood, Chene Royan (University of Calgary, 2024)
Despite new immigrants having higher educational attainment and an immigrant selection policy that admits “the best and the brightest,” one of Canada’s major social policy concerns is the continued deterioration of immigrants’ economic outcomes. This paradox is illustrated by data showing immigrants suffer from higher unemployment, earn less than similarly educated Canadian-born workers, face skill underutilization, and are relegated to the secondary labour market made up of low-wage, unstable jobs, lacking protections such as unemployment benefits. The underutilization of immigrant skills is economically disastrous; it costs the Canadian economy $50 billion yearly. While many studies discuss immigrants' poor labour market integration, offering explanations such as immigrant human capital factors or macroeconomic condition factors, few explore the role of meso-level organizational social actors who decide which immigrants are recruited, shortlisted, and ultimately hired. This dissertation seeks to fill this gap by exploring the role of Human Resource Management (HRM) professionals in immigrant labour market integration in Alberta. Using interviews and critical discourse analysis of HRM textbooks and course outlines, I examine HRM professional's decision-making policies, processes, considerations and constraints when evaluating immigrant applications for jobs. The study reveals that immigrants, particularly racialized immigrants, face barriers to employment in the primary labour market because of the professional and institutional logic of strategic human resource management (SHRM). SHRM promoted in HRM professional education recommends that HRM professionals prioritize business objectives over equal treatment, consideration, and fairness in hiring. SHRM enables unequal power relations between hiring managers (team supervisors) and HRM professionals, which enables cultural racism to go unchecked in hiring. SHRM justifies organizational discriminatory and social closure practices as well as enables the denial of immigrant claims for employment. This is based on the perception that immigrants pose administrative burdens and financial risks stemming from the misidentification of immigrants as temporary migrants and possessing human capital and cultural deficiencies. Hiring decision-makers often do not rely on objective assessments like work sampling tests when making hiring decisions. Instead, when evaluating immigrant job applicants, they rely on racial cultural stereotypes and signals of White Canadian cultural competency as the basis for callbacks and selection.

Temporary Foreign Workers in Canadian Labour and Human Rights Tribunals: A Comparative Analysis - Reid, Taelor (University of Guelph, 2024)
Due to their status, it is difficult for temporary foreign workers to report grievances related to instances of discrimination, exploitation, harassment, abuse, and health and safety violations. While the subject of temporary migrant work and legal action has been studied before, available research focuses on the impacts of high-profile cases at the Supreme Court. As such, there is limited research about the tribunals that handle the grievances of TFWs most often. This thesis fills that gap by presenting a comparative analysis of the fortunes of temporary foreign workers in human rights tribunals and labour tribunals in Ontario and Alberta. This analysis shows the nature and outcome of these hearings have important differences that depend on the tribunal type. More specifically, human rights tribunals seem to be better equipped to assess the grievances of TFWs despite there being a higher volume of TFWs using labour tribunals.

Not Just Nice Guys: The Growth and Constraint of the Nova Scotia Teachers’ Union, 1950-1975 - Robben, Alex (Dalhousie University, 2024)
This study traces the mid-twentieth century history of the Nova Scotia Teachers’ Union (NSTU), with particular focus on the union’s democratic, professional, and bargaining structures. Traditionally underrepresented in labour union histories, teachers’ unions are a keystone public occupation with extremely high industrial density and a complex relationship with numerous levels of government. In the period studied, teachers were paid both by provincial and local governments but were technically only allowed to bargain with the former; this relationship was instrumental in keeping teachers’ demands depressed but was too unstable to contain teacher militancy effectively. Following an interrogation of the union’s restrictive legislative and organizational foundation, the thesis analyzes the adoption of professionalism as a status-raising strategy, but with severe exclusionary tendencies. The thesis continues with a chronological recounting of provincial and local-level negotiations, the contention of which forced the union and the provincial government to renegotiate their bargaining mechanisms.

Navigating Precarious Paths: An Assessment of the Open Work Permit for Vulnerable Migrant Workers - Weeks, Alyssa (Dalhousie University, 2024)
Temporary migrant workers on closed work permits are vulnerable to exploitation and abuse. To address this precarity, the Government of Canada introduced the Open Work Permit for Vulnerable Workers (OWP-V) in June 2019. This permit allows migrant workers in abusive situations, or at risk of abuse, to leave their employers and find new work in Canada for up to 12 months. Drawing from secondary literature, policy analysis and qualitative interviews with migrant support workers and experts, this research assesses the implementation of the OWP-V policy in the Maritimes by examining its benefits and critiques. This research demonstrates that although some perceive the policy as a step in the right direction, significant barriers remain that hinder the effectiveness of the OWP-V in removing migrants from abusive conditions. Further findings demonstrate that even with systemic and technological improvements, stakeholders remain dissatisfied with the policy as it fails to protect migrant workers from re-entering cycles of abuse and exploitation, serving only as temporary relief. To improve the implementation of this policy, stakeholders provided several suggestions pertaining to accessibility, language options, processing times, and inspections. Overall, this thesis argues that while these changes could help improve the working conditions of temporary migrant workers in Canada, substantial systemic issues remain.

The Affective Basis of Judgements and Narratives Surrounding Sexual Commerce in Western Canada in the Late Nineteenth and Early Twentieth Centuries - York-Bertram, Sarah Elizabeth (York University, 2024)
This dissertation undertakes an affective reading of late-nineteenth and early-twentieth century Canadian primary sources through which to analyze the affective basis of judgments and narratives surrounding sexual commerce. Situated in the interdisciplinary subfield of the history of emotions, this dissertation centres sexual commerce as a site of colonial worldmaking in what are currently the southern regions of the provinces of Manitoba, Saskatchewan, and Alberta, and traces emotional through-lines across fields in social space. Beginning with a self-reflexive prologue drawing from a method feminist theorist Clare Hemmings (2011) terms “situated horror,” this dissertation then turns to the Dominion of Canada’s post-1867 westward expansion, its legal mechanisms, and affective mobilizations. Across the empire, Britain tied legislative powers to feelings that reflected its goals, ideal social order, and habitus of its peoples. Like a mathematical equation, peace in the colonies would emerge through order and good government and law-abiding citizens would be its beneficiaries. That equation was integral to the shift from a fur trade economy to a settler colonial one oriented toward a British imperial and Canadian economic disposition. The corollary effect of the equation was the normalization of British and Canadian views on what constituted peace, their conceptions of capital, and the conceptual transplant of disorderly figures, such as the “rebel,” the “vagrant,” and the “prostitute” – or, broadly, people defined as “outlaws.” Three main sites of colonial worldmaking are examined in this work: that of the journalistic field in chapter four, that of the political field in chapter five, and that of the juridical field in chapter six. By tracing emotion in oft-cited, and not-so-oft-cited, primary sources that discuss concerns about and responses to sexual commerce, the emotions underpinning narratives and judgments surrounding sexual commerce become evident. This method offers an emotions history of western Canadian colonial expansion, revealing how sex workers, histories of sex work, and feelings about sexual commerce were integral to Canadian worldmaking. Responses to sexual commerce were informed by the Dominion of Canada’s worldmaking mission, concerns over human unfreedom, and dynamic social positionings in emergent settler colonial society. British imperial and Canadian whiteness were produced through gendered-racialized processes of differentiation at the local, municipal, provincial, federal, and imperial levels. White men’s feelings of satisfaction dominated in this history, as they intensified their gendered monopoly on resources, space, and authority in a region that had been known as Indigenous peoples’ territories. This analysis of masculinized emotions contributes to the feminist theorization of colonialism and sexuality.

Queer Utopian Theory for Transformative Change in Theatre Organizations - Zarrillo, Maria (Royal Roads University, 2024)
Canadian theatre has the potential to incite social change but inequitable working environments within theatre organizations have hindered this prospect. The sector needs new frameworks to improve conditions for arts workers. Inspired by several scholars such as José Esteban Muñoz, Jack Halberstam, and Lee Edelman, I look to the concept of queer utopia to address inequities within the theatre sector, with a focus on the role of theatre organizations. By defining Queer Utopian Theory (QUT), analyzing calls to action in the Canadian theatre sector, and employing three focus groups, I created a Queer Utopian framework for Canadian theatre organizations to answer the research question: What is the utility of the concept of queer utopia in addressing inequities in the Canadian theatre sector? My research found that relationship building, embracing fear, and subverting socio-political norms are aspects of QUT that are of utility to organizational leaders who wish to foster equitable environments.

From the Voices of Mexican Seasonal Farm Workers in Alberta - Barba González, Maricruz (University of Alberta, 2023)
In response to labour shortages across various sectors, including agriculture, the Government of Canada created the Temporary Labour Program, one stream of which is the Seasonal Agricultural Worker Program (SAWP). Mexico is currently the major partnering country, which runs the matching Programa de Trabajadores Agrícolas Temporales (PTAT) which accounts for 43.8% of all migrant seasonal farm labourers in Canada (SRE, 2022). With the increasing number of migrant workers in Canada, there are growing concerns about their labour and living conditions. Loo (2014) and other authors contend that to improve international labour programs so as to better serve foreign workers, it is critical to learn migrant workers’ perspectives by having their voices heard. There are, however, challenges to speaking with foreign farm workers, including language differences, rural locations, long workdays, living constraints, and fear of speaking out. Most research on migrant workers has been conducted in Ontario, Quebec and British Columbia, which have the highest provincial numbers. Conversely, there has been little research examining migrant workers’ experiences in the province of Alberta. My qualitative, participatory research contributes to the literature by exploring the perspectives of Mexican seasonal agriculture workers who have participated in the PTAT in Alberta. I used a focused ethnographic approach and methods of PhotoVoice and semi-structured interviews to learn about their motivations for enrolling in the PTAT and their experiences of working in the agriculture sector in this provincial context. Participants' narratives and photographic images provided information about: their motives for enrolling in the PTAT; how they navigated the application process; their lived experiences while working on farms and other agriculture businesses in Alberta; the impacts on their health and well-being; and, their perspectives on their role in Canada’s agri-food system. I also explored workers’ perspectives on being part of this international labour program during the COVID-19 pandemic and how this influenced the different stages of their experiences, both in Mexico and Canada. As part of the investigation of participants’ perspectives on health and well-being, I asked them about their access to health services and healthy and culturally appropriate food, and opportunities they had to experience community life in Alberta. Many of the findings from this research align with previous studies illuminating the vulnerable and challenging working and living conditions of migrant agricultural workers in Canada. Novel insights gained through this participatory research with Mexican migrant agriculture workers in Alberta focus on the application process and institutional context in Mexico, workers’ perspectives on their health and well-being, and their narratives and photographic images about their lived experiences in Alberta during the COVID-19 pandemic.

“Short-Term Band-Aid Solutions”: A Feminist Analysis of Family Caregiving and Caregiver Immigration Policies in Canada - Champagne-Holland, Morag (University of Victoria, 2023)
Throughout Canada, the need for care provision services is on the rise. The number of people willing and able to provide these care services is insufficient to address the growing need for care. Care work is provided by a mix of paid workers and unpaid family members. The majority of both these groups of care workers are women. Care work has long been undervalued as feminized labour, resulting in insufficient government support for family caregivers, and persistent labour issues within paid care sectors. In this thesis, I explore two distinct sets of Canadian federal policies related to care provision – Employment Insurance (EI) benefits for unpaid family caregivers, and the Home Child Care Provider and Home Support Worker Pilot Programs, which facilitate the immigration of private in-home caregivers to Canada – in order to discover whether they are underpinned by a shared set of similar assumptions about the nature of care work, who is best suited to perform it, and how it should be provided. In examining the assumptions about care that underpin and shape these policies related to care provision in Canada, I identify a number of consistent gendered themes about care and care providers and analyze their impact on policy outcomes.

The Politics of Low Pay: Corporatism, Left-Wing Parties and Low-Wage Workers - Durocher, Dominic (University of Ottawa, 2023)
Politics has often been conceptualized as a conflict between political parties that represent the economic interests of different groups in society. This conception of politics has, however, been considerably weakened by the economic and social transformations of the last decades and by the rise of post-materialist values among newer generations of electors. Indeed, the vote of manual workers for left-wing parties has declined significantly in recent decades as did the impact of left-wing parties on social spending. At the same time, the issue of low-wage work has become prominent in the partisan debates of several countries such as the United States, Canada and the United Kingdom following the mobilization of low-paid workers, unions and community associations. Low-wage workers who mainly work in the service sector have often precarious work and living conditions following decades of labor markets deregulation and are highly dependent on governmental policies to insure decent living and work conditions. One of these policies, the minimum wage, has been at the center of the electoral campaigns of many left-wing parties in recent years. However, the issue of low-wage work has rarely been studied in political science. This thesis seeks to explain the partisan dynamics surrounding the issue of low-wage work. My main argument is that low-wage workers tend to vote for left-wing parties in accordance with their economic interests, especially in countries with a weak degree of corporatism such as the United States and the United Kingdom. In those countries, left-wing parties have strong incentives to make pledges related to low-wage work like increasing the minimum wage in their electoral manifesto, because unions are unable to negotiate decent working conditions for the majority of workers. Indeed, in countries with weak corporatism, low-wage workers are very dependent on governmental interventions to ensure minimum working standards and improve their living conditions. In countries with strong corporatism, however, unions negotiate collective agreements that ensure minimum working conditions for the majority of workers, workers with weaker bargaining power are thus less dependent on government policies to insure decent working conditions. Therefore, left-wing parties should be able to consolidate their vote among low-wage workers in countries with a weak degree of corporatism. Once in power, left-wing parties should also increase the minimum wage and the direct cash transfers to low-income families more than governments led by right-wing parties, especially when corporatism is weak. The emphasis on policies targeted to low-wage workers by left-wing parties in countries with a weak degree of corporatism could also limit the capacity of radical parties to attract the vote of low-wage workers. This thesis is composed of 4 articles, one on electoral pledges related to low-wage work, one on the vote of low-wage workers, one on the impact of left-wing parties on minimum wages and one on the impact of left-wing parties on direct cash transfers received by low-income families. These four articles demonstrate the relevance of a materialist conception of politics and the role of institutions regulating the labor market on partisan dynamics.

College Contract Faculty in Ontario: Professional Identities and Precarious Employment - Fick, Emmanuelle Eve (University of Toronto, Ontario Institute for Studies in Education, 2023)
Partial-load college faculty simultaneously occupy insider/outsider positions in their respective higher education institutions. How do they perceive the relationship between their employment status and their work as educators? In recent scholarship, it has been argued that part-time faculty occupy liminal positions as simultaneous professionals and precarious labourers in higher education. None of the literature attends to how part-time college faculty (a cohort that makes up 70%+ of Ontario’s college faculty) who specifically aspire to full-time teaching positions think about their work and professional identities, much less in the context of the province of Ontario, Canada. Through semi-structured and open-ended interviews with ten partial-load college faculty who aspire to full-time teaching positions across three colleges in the Greater Toronto Area (GTA), this study asks faculty to reflect upon the relationship between their conditions of employment and their work as educators. How partial-load college faculty think about their work and professional identities has direct import for what continues to be the foundational mission, purview, and day-to-day activities of colleges – teaching and learning. Holland, Lachicotte, Skinner, and Cain’s (1998) identity theory provides the framework for enabling a nuanced analyses as to how partial-load college faculty think about, make sense of, and narrate their experiences in the liminal space of precarious professionals. The results of this study show that partial-load faculty are largely excluded from the pedagogical communities of their departments and institutions and that every aspect of their work as educators (curriculum development, professional development, and relationships with colleagues) is negotiated and filtered through their precarious status. This research sheds light on the centrality of partial-load college faculty on the enactment of curriculum in colleges as well as explores how various stakeholders can make meaningful change to address the professional goals and curricular inclusion of this significant teaching cohort.

Labour Community Services and the State of Community Unionism in Toronto - Gooder, Austin (McMaster University, 2023)
Community unionism is still contested in the literature, and its presence across various industries and union formations is often not concretely described. This thesis engages in an examination of community unionism within the literature and assesses its potential presence in Toronto’s Labour Community Services, an organization which provides administrative and organizational support to labour unions and community groups in the Greater Toronto Area. Interviews with LCS organizers and staff members and other Toronto labour activists are assessed against common depictions of community unionism within the literature to determine if LCS is engaged in community unionism, or perhaps some other organizational strategies or philosophies. Interviews demonstrated a clear commitment to community building and deepened ties between the labour movement and various formations of community across Toronto and surrounding regions. Interviews also reveal the state of union-community resources, the barriers commonly experienced in this form of organizing, and how organizers and staff members perceive their role in the broader labour movement. Interviews with key informants reveal a series of strategies and choices which shape how Labour Community Services operates. Ultimately, Labour Community Services does not engage in community unionism as a whole practice, but rather utilizes several strategies and operative choices that share common ground with community unionism. A byproduct of these strategic choices is the creation of forms of community unionism between both the labour unions and community groups that LCS frequently works with.

“A New Saskatchewan?”: Political Culture Change in Saskatchewan Party-Era Saskatchewan - Hill, Lauren (University of Alberta, 2023)
Since its founding as a province, Saskatchewan has been depicted by the academic literature as possessing a political culture that was distinctly collectivist, dirigiste, protectionist, and polarized, largely owed to the historical political dominance of the Co-operative Commonwealth Federation (CCF) and the New Democratic Party (NDP) in the province. Such narratives have outlived the political fortunes of both the CCF and NDP, and have, until this point, persisted despite the rise of the right-wing Saskatchewan Party. This thesis aims to fill a scholarly gap, through considering the influence of prolonged Saskatchewan Party governance on the province’s politics and assessing the current state of Saskatchewan’s political culture. Specifically, I ask the following question: what is the dominant political culture strand in Saskatchewan Party-era Saskatchewan? Through a series of online focus group activities involving people from across the province, I assess and substantiate the influence of political culture pillars, such as collectivism, laissez-faire, heartland, and adversarialism, in shaping Saskatchewan’s provincial identity and contemporary political culture. This study demonstrates that Saskatchewan’s political culture has changed. Specifically, this thesis finds Saskatchewan’s contemporary political culture to be ‘blended’, containing components of both traditional and alternative political culture strands, although displaying a slight preference for the neoliberal and conservative alternative political culture. The findings suggest that the current Saskatchewan political culture has departed from its collectivist and hinterland traditions in favour of individualism and heartland. Meanwhile, the political orientations towards the provincial government’s role in the society and the economy (dirigisme or laissez-faire) or the attitudes Saskatchewanians possess towards political actors and the political system (adversarialism or pragmatism) are considerably more varied and lack ideological consistence. Ultimately, this study highlights the influence of political party shifts in serving as mechanisms and reflections of political culture change and provides an overview of Saskatchewan’s contemporary political culture under prolonged Saskatchewan Party governance. A concluding discussion highlights the value and significance of this research and suggests area of future exploration about Saskatchewan provincial politics and political culture.

Honouring Grief Experiences in Life, Death, and the Workplace: A Critical Analysis of Bereavement Accommodation for Workers in Precarious Employment in Canada - Joy, Karima (University of Toronto, Dalla Lana School of Public Health, 2023)
Bereavement scholarship predominantly explores psychological aspects of grief, which neglects the role of social, economic, and political factors that shape the space allotted to accommodate these experiences. The current Canadian social context offers minimal space to honour bereavement as a part of the human condition. Aiming to respond to calls for enhancing bereavement care, this dissertation explores bereavement accommodation for workers in precarious employment in Ontario, Canada. Drawing on critical qualitative research and feminist ethics, this study employs policy analysis and in-depth interviews to generate multi-scalar knowledge on the everyday experiences of bereaved workers in precarious employment. I argue that there are discrepancies between how bereavement is represented in the social context and the everyday experiences of bereaved workers. The current representation portrays bereavement as a short-term, workplace disruption, neglecting grief and many forms of practical and emotional labour in bereavement. Participants expressed they were uninformed and unprepared for grief and bereavement labour, and that navigating the current context created tension, stress, exhaustion, isolation, and stigma. I argue we need a collective, ontological reckoning with our sense of autonomy, recognizing and honouring our interdependence in life and death. I argue that bereavement is a neglected public health issue driven by socio-political forces that devalue relationality, stigmatize emotions, and render bereavement an individual responsibility. This thesis makes broad recommendations for a public health approach to bereavement care, including enhancing grief literacy, creating more responsive care pathways and strategies for addressing individual and collective grief, and establishing safeguards for precarious workers.

The Thicker the Agreement, The Poorer the Relationship: An Examination of Public Sector Environments in Canada and the Intersection of Organisational Trust, COVID-19, and Collective Bargaining Agreements - Lawton, Teigan R.G. (Australian Institute of Business, 2023)
In late December 2019, a new and emerging coronavirus came out of Wuhan, China. The severe acute respiratory syndrome coronavirus 2, widely known as “COVID-19” (WHO, 2022), significantly impacted nearly every aspect of human life on Earth. This study, referred to throughout the thesis as a “project,” examined the intersection of collective bargaining agreements and COVID-19 in unionised environments in the public sector of Canada. --From Executive Summary

Building Blocks of Victory in Oshawa 1937: The Left, the Rank and File, and the International Union - Leah, Anthony D. (McMaster University, 2023)
The Oshawa 1937 strike against General Motors was a major turning point in Canadian labour history. This thesis explores the factors that led to its success, including the historical background of working class struggle; the economic and political context of the times; prior organizing by Communists; the engagement of rank-and-file GM workers and the remarkable stewards’ body they established; and the support and leadership of the UAW International union. The influence of Communists meant that the strike incorporated many features of what might now be called rank-and-file unionism: industrial unionism, democratic engagement of rank-and-file workers, militancy on the shop floor, building solidarity within the workforce and in the community, international solidarity, and rejecting cooperation with corporations. The contending forces of workers, corporations, and rabidly anti-union governments that clashed in Oshawa in 1937 are largely the same ones we see in the battles going on in North America today. Thus, understanding the factors that led to the success of the Oshawa strikers can provide valuable lessons to those seeking to revive today’s labour movement.

Provincial Bargaining, Provincial Union Power, and the Ontario Secondary School Teachers’ Federation: A Case Study of Ontario Teacher Union Democracy in an Era of Centralized Bargaining - Mancini, Chantal Yvonne (McMaster University, 2023)
This thesis explores the impact of the centralization of bargaining in Ontario’s education sector on the internal democracy of the Ontario Secondary School Teachers’ Federation (OSSTF), the province’s second-largest teacher union and self-described defender of public education. Using multiple theoretical lenses of union democracy, public sector unionism, labour geography and teacher professionalism, this thesis examines OSSTF’s history and the evolution of its internal processes and structures, with a focus on the union’s response to the gradual shift to a centralized bargaining regime. Initially formed in 1919 as a conservative organization committed to raising the professional status of teachers, OSSTF expanded into a union that represents both teachers and support staff, bargaining contracts for members with local employers. Positioned within a public sector context of austerity and neoliberal governments looking to contain the costs of public education, OSSTF found itself subjected to legislation intended to upscale education funding and bargaining, beginning in the late 1990s. This thesis finds that the external context of centralization of bargaining has been the most important factor in shaping the internal democratic life of OSSTF, shifting scales of power from the local to the provincial level of the union, exacerbating tensions between provincial and local actors, increasing the overall bureaucracy of the organization, and reducing democratic participation by the rank-and-file. These findings lead to the greater question of whether these internal changes have enhanced or limited the ability of OSSTF to effectively further their members’ interests and resist the neoliberalization of the school system, with a view to considering the role of teacher unions within the future of public education in Ontario.

(De)constructing Nation and Race Along the Canadian Pacific Railway: First Nations and Chinese Migrants in the Colonial Project - Petrie, Emilee (University of Victoria, 2023)
Much has been written on the history of the Canadian Pacific Railway (CPR), but rarely are conversations regarding the experiences of First Nations and Chinese immigrants on the railway brought together. This thesis will analyze how First Nations and Chinese people in Western Canada experienced the construction of the railway and how, as racialized peoples, they were excluded from the original national mythology centered on the completion of a transcontinental railway. The seemingly benign symbol of a railway representing the nation continues the violence of naturalizing colonial, capitalist structures in the national landscape. A closer look at this history reveals the dispossession of Indigenous peoples, the destruction of their ways of life and incorporation of the capitalist economy—all processes that continues today. The history of the railway also reveals the place of Chinese immigrants as a distinct, racialized labour force in late-nineteenth-century Canada that reinforced and that was informed by the racial and economic interests of the national subject at an important time in the development of the nation and its national myths. Drawing on the insights of Manu Karuka’s Empire’s Tracks, this analysis situates the CPR as a tool of colonial, capitalist, countersovereignty.

Syndicalisme au Québec et rapport à la société civile : sociologie historique de la trajectoire clérico-nationale de la CSN - Scott, Jonathan (Université du Québec à Montréal, 2023)
L’intuition sociologique qui a orienté notre démarche de recherche se présente ainsi : pour saisir la trajectoire de l’histoire du syndicalisme en sol québécois, de son émergence à sa représentation actuelle, il importe de lier cette évolution au processus d’émergence et de transformation de la société civile. Afin de travailler cette intuition, nous avons revisité l’histoire du syndicalisme en nous concentrant sur ce que nous nommons « la filiation clérico-nationale », laquelle définit l’identité de la CSN. Ce travail s’avère essentiel pour nous permettre de compléter les analyses d’historiens sociaux et de sociologues des relations du travail en proposant une lecture sociologique nouvelle des périodisations existantes de l’histoire du syndicalisme québécois. Cette intuition nous demandera de qualifier l’évolution récente du syndicalisme québécois du fait qu’en contexte néolibéral, le répertoire d’action du partenariat social, défini à l’aube des années 1980, s’est essoufflé parce qu’il est non seulement soumis à rude épreuve, mais aussi parce qu’il peine à se renouveler. Sur ce point, des auteurs voient dans la baisse du taux de syndicalisation des personnes salariées des pays développés une preuve validant l’hypothèse d’un affaiblissement du syndicalisme. De plus, en sol québécois, malgré une stabilisation du taux de syndicalisation autour de 38%, les syndicats donnent l’impression d’avoir perdu de leur capacité d’être la composante de la société civile la plus représentative auprès du législateur québécois. En qualifiant l’évolution récente de la CSN, nous avons été en mesure de montrer qu’il y a eu recomposition de la centralité des capacités d’action d’une composante importante du mouvement syndical québécois. À partir d’une méthodologie partagée entre la recension d’écrits et l’analyse de contenu de documents de la CSN, nous répondrons aux questions centrales que nous nous sommes posées et validerons ou invaliderons nos hypothèses de travail. Notre thèse nous permettra de proposer une périodisation enrichie de l’action syndicale québécoise. Cette « nouvelle périodisation » apportera des précisions sociologiques aux périodisations historiques existantes. Elle le fera en fournissant des éclairages nouveaux sur les conditions d’émergence du syndicalisme, sur son évolution et surtout, elle abordera la période contemporaine correspondant aux quarante dernières années. De plus, en concentrant notre travail sur la filiation clérico-nationale, nous mettrons en lumière le caractère historique de la posture de concertation et de collaboration des organisations syndicales québécoises : de son émergence à son renouvellement actuel. Plus précisément, l’analyse des données que nous présenterons sur la période récente fournira des éléments clés pour saisir la particularité du syndicalisme québécois. Ce dernier se développe, selon notre lecture, de façon symbiotique. L’amorce de cette relation symbiotique est clairement apparue avec la première configuration développementale, laquelle prend naissance dans les années 1930 sous le leadership du haut clergé québécois. Depuis, cette relation symbiotique s’est maintenue et a été développée au fil des mises à niveau du modèle québécois de développement. De nos jours, elle prend une couleur particulière que nous avons qualifiée de partenariat social stratégique. Notre étude de la CSN illustrera comment les logiques d’actions de cette organisation sont partagées entre la collaboration avec le capital, l’État et des organisations de la société civile, tout en mobilisant, au besoin, la conflictualité. Nous montrerons comment, au fil des quarante dernières années, les discours de la CSN font état d’une relation ambidextre avec les grands secteurs institutionnels. Une relation qui est partagée entre collaboration et conflictualité tout en étant teintée de développementalisme. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : CSN, histoire sociale, institutionnalisation, logique d’action, néolibéralisme, société civile, syndicalisme

The Framing of Temporary Foreign Workers in Canadian Parliamentary Debates - Shaheen, Tartil (University of Windsor, 2023)
This study examines the framing of temporary foreign workers (TFWs) and the Temporary Foreign Worker Program (TFWP) within the context of Canadian political discourse. Through a qualitative content analysis of parliamentary speeches spanning from 2006 to 2022, it investigates how TFWs and the TFWP have been framed by members of three federal political parties: Conservatives, Liberals and the NDP. With an aim to understand influences on framing strategies, the analysis considers significant events such as the COVID-19 pandemic and a change in government. The findings highlight the significance of party ideology in shaping perspectives on TFWs and the TFWP, with all three parties recognizing the necessity of this group and program in achieving Canada’s economic goals. At the same time, despite their increasing significance in the economy, the study highlights the conditional inclusion of TFWs in Canada. Policymakers adapt their frames based on perceived contribution of these workers and their alignment with Canadian interests. This research illuminates the crucial role of framing in shaping policy outcomes regarding TFWs and the TFWP.

Enabling Settler Citizens: Disability, Age, Public Health, and Settler Colonialism in Northern Ontario, 1876-1951 - Wiener, Leah (Simon Fraser University, 2023)
My dissertation analyzes the relationship between public health and settler colonialism, employing age and ability as key categories of analysis. I argue that settler colonialism and public health were constitutive of one another. Public health policy weaves together notions about land, race, labour, age, and ability, to structure and stratify societies. Public health relied on white supremacist tropes to justify the state's attempts to subjugate and dispossess the Anishinaabeg in Northern Ontario. The idea of a "public" was critical and contested in the intersection of policy and the emerging social science of public health. Settler standards of public imagined a "public" that was white, male, middle-class, and adult, with a body that could be made healthy through individual effort. Settler ideas about Indigenous Peoples shaped the "public" as a racialized and age-stratified concept in Canadian public health and health policy. In this dissertation, I seek to highlight how material and symbolic age, and material and symbolic children, figured in settler-colonial processes of state formation in the context of public health policies. I examine how bureaucrats and institutions in the public and voluntary sectors constructed and portrayed Indigenous and settler health, measuring each against a middle-class standard of "public" health. To do this, I set forth four interconnected arguments. First, settler colonialism and settler public health policy were mutually constitutive. Second, disability existed alongside and entangled with age as a key framing for settler public health policies. Third, these public health policies drew from a bifurcated notion of the "public," resulting in policies focused on protection and surveillance based on racialized lines. Finally, these framings of disability, age, and the "public" had clear material impacts in Northern Ontario's settler-colonial context, enabling settlement while dispossessing Indigenous Peoples.

Comparing Public Secondary Teachers in Ontario with Different Labour Contracts in a Time of Crisis - Wilkin, Andrew (McMaster University, 2023)
This dissertation compares the work and life of secondary public-school teachers in Ontario with different labour contracts during a time of crisis. The COVID public health crisis along with neoliberalism, the defunding of public education, and a climate crisis have all influenced governmental policies and the labour process of public secondary teachers in Ontario. The influences that different contracts can have on the labour process of teachers, how they feel towards their union, and the impacts on their individual health and household wellbeing before and during the first year of the COVID pandemic is the focus of this dissertation. To help explore these contexts and the influences on the life and labour of public secondary teachers in Ontario with different contracts, I have used research from studies in Labour Process Theory, precarious work, and educational labour to inform my analysis. Along with those areas of discourse, I have also used insights from research into Critical Realism and Thematic Analysis to think through and discuss the differences between the teachers I interviewed and connect their experiences with work, their union, and their individual health and household well-being to larger systems, structures, and histories. The interviews conducted revealed three points of interest: that precarious labour contracts can function as a disciplinary device, that larger contexts outside the contract shaped how the contract was experienced, and that teachers’ unions can act as a source of solidarity and security during a crisis and when there are certain associations with its purpose. This exploratory research aims to open up future areas of research into educational labour and differences between the experiences of educators with different contracts.

“You Appear Silent to People Who Are Deaf to What You Say”: Solidarity, Schisms, and Alterity in Immigrant Women’s Political Organizing in Toronto, 1970s-1990s - Aguiar, Julia Elizabeth (Queen's University, 2022)
This thesis considers the connections between the increased migration of racialized women to Canada and the ascendancy of social movements in Toronto from the 1970s to the 1990s. In the mid-1970s, there was a surge of grassroots organizations founded by and for immigrant women in Toronto. They were established to address the distinct needs and experiences of immigrant women where government and preexisting, decidedly hypermasculine, ethnocultural organizations did not. This thesis argues that these organizations, and the individuals associated with them, were fundamentally political. In situating these organizations within the broader progressive political landscape of Toronto, this thesis elucidates the ways in which immigrant women’s political organizing challenged and transformed dominant social movements. In particular, immigrant women’s fraught relationship to the mainstream women’s movement in Toronto is closely examined. I argue that immigrant women organized both within and without the Toronto women’s movement. In their relationship to the women’s movement, immigrant women contested the limited perspective of white feminism by drawing closer attention to class and race. This was most evident within immigrant women’s organizing for reproductive freedom. Additionally, immigrant women organizer’s relationship to the Canadian state is analyzed as a site of struggle which dialectically constrained and sustained their activism. Because immigrant women worked in higher numbers than their Canadian counterparts and often in exploitative sectors, labour became a central issue within their activism. Through their labour organizing, immigrant women forged important alliances with the labour movement. This thesis also attends to the uneven racialization of immigrant women which informed their activism. Immigrant women’s activism offered alternative perspectives and methods of organizing which did not conform to dominant ones. By taking a relational rather than assimilationist or pluralistic approach to the relationship between immigrant women’s organizing and broader social movements, a fuller, more nuanced portrait of the intersections between immigration, gender, race, and social movements can emerge.

Craft Capitalism: Labour and the Narratives of Artisanal Production - Anderson, Benjamin (Simon Fraser University, 2022)
In the last decade, considerable attention has been paid to the category of craft. Within the disciplines, particularly in sociology and art theory, scholars like Richard Sennett, Susan Luckman, and Glenn Adamson have attempted to define, theorize and delineate the history of craft and its influence in contemporary capitalist culture. Popularly, books and television shows feature the work of makers and craftspeople, their popularity compounded by online crafting communities like Etsy. For all of this attention, considerably less has been paid to the labour that creates the craft products to begin with. This dissertation interrogates the category of craft from a critical labour studies perspective, first by analyzing its labour process, and, second, by amplifying the voices of workers in these industries in order to reflect the conditions they face, their attitudes about craft, and their reflections on class and organizing. In order to accomplish both, the dissertation reports on participant interviews and critically examines cultural artifacts concerning so-called making (typically understood as amateur or semi-professional small-scale production) and craft industrialism (used to define scalable industries that use craft branding and terminology). Its key case studies are making/makerspaces and craft brewing in the Cascadia region of North America, although it also visits the roasteries, bike shops, and bakeries that make up some of the other primary sites of the artisanal economy. This dissertation makes four primary contributions to the critical study of craft. First, it reorients the common approaches to craft, which either prioritize craft objects or individual maker activity. By redirecting attention to the social process of production, it avoids the object-orientation of many approaches as well as the maker-as-virtuoso narratives of popular accounts. By focusing on the social dynamics of craft, the dissertation transcends the singular craftsperson to make its second contribution: the reconceptualization of skill as social category rather than individual attribute. This social approach to skill paves the way toward the dissertation's third contribution: a dialectical consideration of the craftworker as distinct from but intrinsically related to the craftsperson. Analysis of cultural artifacts and discussions with workers highlighted the dependency of craftsmanship and support work. Finally, the dissertation distills maker and worker attitudes into a set of observations regarding the maker movement's narratives of emancipation through self-directed work as well as the potential of solidarity in craft industries.

Indigenous Workers and Trade Unions: Settler-Colonial Capitalism, Indigenous Peoples' Labour and Union Engagement - Karim, Alia Neisha (York University, 2022)
It is only in the last few decades that Canadian trade unions have expressed labour solidarity with Indigenous peoples by bringing their attention to the distinct concerns of Indigenous workers in the workplace and beyond it. Trade unions have taken important steps to express support for their Indigenous members and their communities, yet little is understood about Indigenous peoples’ experiences in the capitalist labour market shaped by land dispossession, the ongoing manifestations of settler-colonial oppression, and the systemic economic marginalization by Canadian institutions and employers. It is pertinent to identify what unions are doing to support them and where they can strengthen labour solidarity so that they can develop critical sites of resistance against colonial-capitalist power. A closer analysis is needed to understand Indigenous peoples’ relationships to unions, relations between Indigenous and non-Indigenous working people, and the challenges for unions to build united struggles with Indigenous peoples. This study examines the spaces of union engagement with Indigenous workers and their communities amongst the challenges presented by the reality of ongoing colonial oppression in Canada. The purpose of this study is twofold: 1) to examine the roles that trade unions have had with Indigenous peoples in the paid labour market and recent initiatives that they have taken to meet the needs of Indigenous workers and unionists, and 2) to analyze the ways trade unionists understand and approach Indigenous peoples’ concerns and anti-colonial struggles within the broader confines of settler-colonial capitalism, and to determine the challenges to transforming their practices of solidarity with Indigenous peoples. This study draws upon semi-structured, indepth interviews with 22 Indigenous and non-Indigenous key informants who are elected trade union officials, staff, and rank-and-file unionists. The study’s findings reveal emerging activism of Indigenous workers within their workplaces, unions, and beyond, and the complexities between Indigenous peoples’ relationships with paid labour, unions, and struggles for selfdetermination. I argue that unions are turning their attention to support the distinct needs of Indigenous workers and to support anti-colonial struggles, but they are limited to redressing the effects of settler-colonial capitalism. They face difficulty engaging in solidarity due to the structural limitations of settler-colonial capitalism. By reflecting on participant insights into these challenges, this study proposes an anti-colonial framework for unionists to transform their practices of labour solidarity.

Just in Principle?: Assessing the Contributions of Organic Farming to Socio-Ecological Sustainability in Canadian Agriculture - Klassen, Susanna (Susanna Elsie) (University of British Columbia, 2022)
Agriculture is at the centre of society’s most pressing sustainability challenges, including food insecurity, climate change, ecological degradation, and social inequity. Organic agriculture, when practiced according to an ethic grounded in ecology, health, fairness, and care, has been proposed as a remedy to these challenges. Building on a movement for an alternative to socially and ecologically exploitative food production, organic agriculture is now a multi-billion-dollar industry with established legal and regulatory frameworks around the world. While this growth could be seen as a success, empirical research has called into question the extent to which organic agriculture and market-oriented third-party certifications can foster sustainability transitions and has found that performance is often context dependent (e.g. depending on which practices are adopted). There remain significant gaps in knowledge about how organic agriculture is practiced in jurisdictions around the world relative to the sustainability-related principles on which it was founded, especially the principle of fairness. To address these gaps, I developed a mixed-method assessment grounded in a critical realist methodological approach to evaluate the contributions of organic agriculture to socio-ecological sustainability in Canada. I utilized both qualitative and quantitative methods—drawing from interviews with farmers, inspectors and organic policymakers, analysis of census data for farms across Canada, surveys of vegetable farmers in British Columbia and organic policy documents—to investigate how organic agriculture is shaped and enacted by organic community members at multiple scales. My analysis of organic standards in North America, along with census and survey data in Canada, provide strong evidence for higher levels of adoption of ecologically sustainable management in organic agriculture relative to all other farms. Yet, despite explicit attention to the principle of fairness in organic standards and among organic community actors, I found little evidence that organic agriculture in Canada is correlated with improved working conditions for farmworkers in practice. Across Mexico, the US and Canada, no organic standards contain any requirements related to social sustainability. At the same time, standards governance and community-led efforts toward integrating the principle of fairness into certification show potential to advance a more just and sustainable agriculture.

A Critical Analysis of the Construction of the New Essential Worker Through the Discursive Practices of the Canadian News Media During COVID-19: Implications for Occupational Rights - Kupidy, Steven (Dalhousie University, 2022)
The COVID-19 pandemic and subsequent government responses resulted in a shift in the identity of the essential worker that now included low wage essential workers. Using a critical discourse analysis methodology written news media texts were analyzed revealing various discursive strategies were utilized to construct the new essential worker identity. Findings revealed a fluid, complex identity that was politicized to advance other issues. The need to re-frame the definition of the essential worker was discussed along with the implications on the attainment of occupational rights for low wage essential workers.

The Anti-Conscription Movement in BC and Its Contribution to the Labour Revolt of 1918-19 - Latimer, Brian (Simon Fraser University, 2022)
Historians have generally interpreted the conscription crisis of 1917 as reflective of contending nationalist perspectives in Canada. In contrast this study examines the pivotal role of the labour led anti-conscription movement which developed in British Columbia and throughout Canada in World War One to oppose the threat poses by conscription and other war time acts of repression by the Borden government. A careful study of primary sources and newspapers of the era show that this movement of resistance to conscription also included others threated by conscription: conscientious objectors, Indigenous nations, farmers, and pacifist social gospel activists. The resistance movement had the effect of changing Federal government policy on conscription during the war and changing the political environment after the war and acted as a catalyst in helping to spark the post-war labour revolt.

The Decline of the International Ladies’ Garment Workers’ Union: Shifting Workers’ Identities in Montreal and New York City - MacDonald, Katherine (University of New Brunswick, 2022)
A part of the labour movement for ninety-five years, the International Ladies’ Garment Workers’ Union (ILGWU) worked to better the conditions of garment workers across North America. Although they saw gains for workers in the garment industry over fifty years of progress, in the last forty years of the ILGWU’s history, the union faced a dramatic decline. Large membership losses and a weakening of negotiating power in the industry left the ILGWU a shell of their former self. What happened to this union? This declension did not begin with rapid membership decline, but a steady drop in members was a symptom of missed opportunities and misunderstandings on the part of union leadership of the increasingly diverse needs of garment workers across North America. Using the ILGWU in Montréal and New York City from the 1960s to the 1980s, this dissertation highlights the intrinsic difficulties of with transnational unionization efforts in the late 20th century. The ILGWU’s could not maintain a collective identity for garment worker across North America. Shifting identities made it difficult for the union to maintain their membership and motivate nonunionized workers to join the organization. The decline of this powerful and important labour organization offers critical insights into women’s history and labour activism at the end of the 20th century and reveals new elements of the history of capitalism, especially as it relates to ethnicity and gender.

The 1907 Anti-Asian Riots: The Making of Sensibility Among Working Class Men - McKeen, Patara (University of British Columbia, 2022)
This research explores how racialized sensibility emerged through the 1907 anti-Asian riots in Vancouver and links the riots in Vancouver to the riots in Bellingham earlier in the same year. It uses mixed methods to collect data on portraits, photographs, images, editorials, and documents, employing archival ethnography to read documents along and against the grain (Stoler, 2002; 2012) to make sense of the time period and the sensibilities that underpinned the riots. Archival ethnography helps bring to light the accounts, conversations, and dialogues of colonial agents and actors, and to interpret missing data in the archive. Missing data in the archive consists of historical documents that are overlooked, misinterpreted, or destroyed. My thesis also accounts for gaps, silences, and erasures in the archive by applying critical fabulation to rearrange and reconstruct intersecting viewpoints (see Hartman, 1997; 2008; 2019). To provide a thicker analysis of archival documents, this research interprets olfactory and auditory senses as integral to the making of these riots (see Simmel, 1908/2002; see Campt, 2017; see Lee, 2010; see Mawani, 2009; see Russell, 2019; see also Blaikie, 2002). It is only through the process of combining mixed-methods, theory, and practice that the missing data in the archive can be reimagined and written as part of the historical narrative.

Art, Work: Subsumption, Posthumanism and Artistic Responses to Surveillance Capitalism - Mirzayan, Anna (Western University, 2022)
This dissertation brings together multiple discourses, including surveillance studies, autonomist Marxism and posthumanism, as the groundwork for a novel discussion of contemporary visual art— in particular surveillance art, that is, art that addresses and problematizes the omnipresent digital monitoring now part of everyday life. Because in this dissertation contemporary art is defined as necessarily political, aesthetic (in the Kantian sense) and responsive to conditions of current history and society, I use Marxist theory to identify the particular features of contemporary capitalism that this art is responding to. I first characterize post-Fordist capitalism, focusing on the increasing reliance on extracting network value from what Maurizio Lazzarato called immaterial labour. I discuss Marx’s theories of formal and real subsumption vis-a-vis their impacts on production, technology and subjectivity, and conclude that we need a new term that adequately emphasizes the novel imbrication of technology and subjectivity. In particular, I claim that surveillance capitalism, rising from military technologies and research, characterizes capitalist valorization under hypersubsumption. I then look at the impact of surveillance on labour and subjectivity, with a particular focus on unwaged immaterial activities. Do these activities count as work? To answer that, I propose looking at a combination of Marx’s concept of unproductive labour with a modified type of constant capital. I conclude that the effects of hypersubsumption on labour, consumption and production have produced a new type of capitalist subjectivity: coerced posthumanism, which I contrast with Marx’s authentic species-being. In order glimpse a post-capitalist species-being, I articulate a theory of contemporary art by bringing together Jacques Rancière’s dissensus with Peter Osborne’s notion of contemporary art; both theorists show how contemporary art is necessarily political— what’s more, it is oriented towards an open future. I then apply their ideas to particular artists who have responded to capitalist surveillance by creating ‘artveillance’ (art about surveillance). I evaluate the political effectiveness of three categories of artveillance as experiments in post-capitalist sensoriums.

Race to the Bottom? : A Critical Analysis of Canada's Modern Slavery in Supply Chain Legislation - Sicoli, Angelo (Université d'Ottawa / University of Ottawa, 2022)
This study critically examines the Government of Canada's conceptualization of transnational corporate accountability and exploitative labour in its legislative response to modern slavery in global supply chains. With a primary focus on the government's recently proposed Bill S-216: Modern Slavery Act - which would mandate companies to report on their activities to reduce modern slavery in their supply chains - empirical data is drawn from parliamentary debates about this bill and its earlier iterations as well as a report produced by the House of Commons committee originally charged with studying the issue. Informed by the corporate crime and business management literature as well as a neo-Marxist theoretical lens that employs such concepts as Antonio Gramsci's theory of cultural hegemony and global capitalism, the dominant views taken up in conversations hosted by the Canadian state are captured using critical discourse analysis. Overall, dominant voices accepted into the federal government's approach reinforce neoliberal assumptions of wealth accumulation, profit maximization, and free-market economies, thereby trusting transnational corporations to self-regulate and use their financial capital to curb the conditions that engender exploitative labour. The findings of this interdisciplinary study reveal that the legislative proposal culminating from the policy-making discourse defers to measures that prioritize the social benefits of corporate social responsibility, which ultimately eclipse the need for criminal sanctions against Canadian corporations with operations that employ modern slavery. This research helps to expose the reproduction of corporate impunity as a result of the inability/unwillingness to address the status quo of global capitalism.

Accounting for Racialized Immigrant Workers: Historiography of the Colour Coded System of Disability Exclusion - Simpson, Yvonne Velma (York University, 2022)
Canada’s quest and historical reliance on an immigrant labour force to sustain the nation’s economic and population growth are well established. This has been the case since the formation of New France, where the conquest of people and acquisition of lands and resources, in part, inspired the recording of the first North American census of 1666. However, record keeping practices that commenced in what is now called Canada were part of a larger scheme of a systematic power over governance structure in settler-colonial administrative edicts that cast the foundational structure for inclusion and exclusion criteria based on a colonial racist ideological model of who should be accounted for in the French settlement. As such, Indigenous People were not counted. Similarly, the records of people of Black African ancestry who were brought to New France through the inter-continental routes as enslaved labourers were obliterated from official administrative records. In this first-of-a-kind historiographical query, primary and secondary records of racialized immigrant workers were examined to determine the extent to which Indigenous and racialized immigrant workers existed in governmental demographic records and other sources over time, inclusive of contributions, incurred injuries, disability and fatalities in labour force participation. A purposeful, cross-regional selection of Canada’s occupational health policy experts was engaged in semi-structured interviews on the question of demographic identity, including the intersectionality dimension of race and immigrant status. Insightful findings on the gaps in evolving race-based data collection in the nation’s contemporary occupational health and safety systems were garnered, revealing significant implications regarding the vestiges of colonial determinism in a perpetual colonial system, which underlies the absence of Indigenous and racialized workers from the nation’s informatics on occupational health and safety. Ultimately, this project implicates an urgency for policy changes, aligned with the nation’s persistent reliance on racialized immigrant workers while relegating them to over-representation in work that is more dangerous and injury prone without visible accountability. Dismantling the current policy framework for health and safety by imposing meaningful strategic intervention measures and data collection on ethno-racial demographic identity in the nation's public reporting systems is the resounding outcome of this project.

Great War Profiteering, Patriotism, and the Democratic Revolt in English Canada, 1914 to 1922 - Targa, Ryan (York University, 2022)
In Canadian Great War historiography, the late-war and post-WWI revolt has remained a conspicuous subject for exploring regional and class conflict. This dissertation examines the revolt with a new analytical perspective centred on patriotism and profiteering. The first section of this study constructs a cultural framework called Great War culture. Based on the limitations of the state, it became necessary to militarize socialization so that a major war effort could be undertaken. Through this process, Canada experienced a war-centric cultural shift, whereby social and political belonging became premised on patriotic identity. The term “profiteering” emerged as part of the war-centric lexicon to designate those who were disregarding patriotic sensibilities and selfishly exploiting the war for profit. The second section of this dissertation examines three major interpretations of Great War profiteering between 1914 and 1918: war profiteering, food profiteering, and alien profiteering. It provides an understanding of each controversy through the perspective of federal politicians and state officials; leaders in the labour, farmers’, and veterans’ movements; and ordinary patriots in English Canada. It argues that Borden’s administration failed to curb patriotic outrage and disillusionment, setting the stage for explosive post-war militancy and unrest. The final section examines how workers, farmers, and veterans drew upon the legitimacy of the Great War as a struggle for democracy to challenge the terms of post-war reconstruction. As this section explores, patriots undertook this revolt by using direct action involving violence and industrial militancy. They also used political action to challenge party politics, which some believed to be a root cause of the profiteering evil.

Being Precarious: An Autoethnographic Account of One Precarious Faculty Member's Lived Experience Working in Four British Columbia Higher Education Institutions - Allen, Lisa Marie (University of British Columbia, 2021)
Precarious faculty, once used by higher education institutions as auxiliary labour, now dominate post-secondary campuses. With as much as half of post-secondary institutions’ courses now taught by contract academic faculty, post-secondary institutions have systematically come to rely on hiring precarious contract faculty for their respective departmental teaching capacity. As an emerging and significant trend in higher education, this study aims to examine the precarious faculty experience through autoethnographic methods that reflects on my personal experience as a precarious faculty member working at four different higher education institutions in British Columbia from 2016-2018: the Private Online University, City College, the Teaching University, and the Institute. Using Tierney’s (1997) Organizational Culture Theory, coupled with theories of organizational socialization and the role of models and mentorship, I compare my personal experiences of being hired and onboarded at the four different institutions in which I worked as a precarious faculty member. I focus on three themes: the faculty interview process, being evaluated as a precarious faculty member, and resources that I was given (or not). A literature review precedes each personal autoethnographic account; I then proceed to compare and contrast my personal experiences with that of the literature as a way to examine the ways in which my experiences working as a precarious faculty member are consistent with, and divergent from the literature. To conclude, I suggest that there is a lack of standard processes and practices when it comes to hiring precarious faculty. Additionally, I suggest that one’s career stage plays a significant role during hiring. I also suggest that good student evaluations of teaching lead to reappointment for precarious faculty. In terms of performance evaluations, I stress the importance of communication and suggest that precarious faculty are evaluated (sometimes) both formally, and informally. Finally, in terms of resources, I echo the literature that office space is a place of power, and that professional development is a two-way street. I conclude that more personal stories—like mine—are required to better understand what it’s like to be a precarious faculty member in higher education.

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Concordia University, 2021)
The working-class neighbourhood of Saint-Henri in the Southwest of Montreal was long at the heart of capitalist production in Canada. Like other industrial cities across North America, the area experienced a precipitous deindustrialization and decline in the postwar period, a process whose brutality was matched only by that of the subsequent refashioning of the sector into a post-industrial paradise of restaurants and condominiums. Taking as its point of departure the competing historical discourses at play in present-day Saint-Henri – a post-industrial structure of feeling advanced by developers, business owners, and sanitized heritage projects; an oppositional working-class culture rooted in memories of industrial labour and the hard years of unemployment; and a common, structuring framework of settler whiteness – this thesis uses oral history and archival work to excavate the roots of gendered working-class consciousness, settler identity, and local forms of political resistance in a part of the city long seen as a quintessentially Québécois space. Beginning with the 1967 shutdown of Dominion Textile, the thesis examines the changing patterns of capital accumulation that led to factory shutdowns and the brief 1970s overlap within community organizing around productive and reproductive labour issues, a nexus that conditioned local resistance into the 1990s. It then turns to the State and capital’s conscious redevelopment of the neighbourhood in the image of bankers and hedge funds, a process particularly difficult for the women largely responsible for the affective and reproductive labour of collective survival. Gradually, local activism became integrated into the nationalist State apparatus, as deindustrialization fed into gentrification and the “worker's neighbourhood” slowly became re-imagined as a white-coded “quartier populaire.” Finally, the dissertation turns to a more in-depth investigation of the structuring forces of settler colonialism and anti-blackness on working-class lifeways in Saint-Henri, before concluding with some thoughts on active, public history and the role it can play in imagining transformative ways of organizing local resistance. The dissertation is an intervention into deindustrialization studies, inserting perspectives of race and gender into the discussion; gentrification studies, challenging the field to centre working-class experiences of displacement; Quebec and Canadian labour history, contesting dominant national/ist frameworks; and public history.

'One Day Stronger': A Public History Theatrical Experiment about Remembered Sudbury Strikes, 1958-2010 - Duthie, Richard (Carleton University, 2021)
This dissertation honours and pays tribute to Sudbury residents and many others for whom labour strikes played a significant role in shaping their lives. Set in the context of a public history theatrical experiment, this study investigates local and community memories pertaining to Sudbury mining strikes in the postwar period from 1958 through to 2010. Archival research and oral history interviews were conducted on major labour strikes in this era and that research was used to script, rehearse, and stage a theatrical play. Interviews with audience members and performers were also conducted at all stages of the process. This process allows the dissertation to consider the perspectives of both performers and audience members, each enacting their roles as producers and consumers of public history. The dissertation also assesses the value of this form of history making, as it relates to the formation of historical consciousness, both then and now, of individuals within the Sudbury community. This study argues that public history as theatre has the potential to provide an effective and affecting means to nurture critical, reflexive historical consciousness both on and off the stage.
Keywords: Academic theses; Canada -- History; Public history; Theater; Thèses et écrits académiques; dissertations

The Contested Academy: African Canadian Women’s Experiences as Tenured, Tenure Stream and Non-tenured Faculty - Hylton, Treisha Hanna-Kay (University of Toronto, Ontario Institute for Studies in Education, 2021)
This thesis explores the experiences of Black women who are in tenured, tenure-stream, and non-tenured faculty positions and presents how Black women negotiate their intersectional identities in the academy. The study documents their self-identifications and struggles with the academy in terms of power relations in their respective universities, including racial and sexual discrimination. In addition, the study explores the career paths of Black women faculty from contract faculty to full professor. Methodologically, the study uses Black Feminist theorizing along with autoethnography in order to explore the nature of the experiences of Black Canadian women faculty within the academy. I interviewed 13 self-identified Black women across Canadian universities, including myself as the fourteenth key informant. This study reveals a complex and rich text of how Black women see themselves in the university, their experiences with multiple and overlapping oppressions and how this affects their careers, and finally, their contributions to the academy and their visions of success.

“especially in this free Country:” Webs of Empire, Slavery and the Fur Trade - Lindsay, [Margaret] Anne (University of Manitoba, 2021)
Predicated on a narrative of mutuality and cooperation, what has come to be known as the Canadian fur trade has long been positioned as exceptional in its relationships between colonizers and Indigenous peoples. In this framing the fur trade in what would become Canada is represented as having experienced little of the colonial violence that manifested in other colonial encounters and has been constructed as devoid of the unfreedom of chattel slavery. In fact, this characterization is untrue. Located within the French and British empires, the Canadian fur trade reflected the violences of its empires. From the seventeenth, and well into the nineteenth centuries chattel slavery existed in the fur trade as it did in the empires of which it was a part. Here, as elsewhere, complex webs of family/business relationships carried the violence of empire to and between its colonies. The creation and maintenance of these webs offered spaces where women as well as men could participate in the success of their family/businesses, but also in the transmission of colonial violence. One example of this is the Wedderburn Colvile family, their involvement in both West Indian plantation slavery and in the Hudson’s Bay Company, and in the interventions of one of its members, Jean Wedderburn Douglas, Lady Selkirk in what has become known as the fur trade wars. A closer look at the Wedderburn Colvile family and their interests in the Northern North American fur trade offers insights into how colonial violence and changes in the laws relating to chattel slavery impacted the fur trade, as the effects of these changes traveled along family/business webs of networks of relationship. This research draws on primary sources gleaned from archives and libraries in Scotland, England, the West Indies, the United States and Canada. It brings together a wide range of secondary literature to argue that, just as in other parts of empire, colonial violence, including chattel slavery, connected through webs of family/business relationships, existed in the Canadian fur trade. At the same time, this project argues, the erasure of that story is something we are only now beginning to address.

Making Ukrainian Canadians: Identity, Politics, and Power in Cold War Canada - Luciuk, Kassandra Larysa (University of Toronto, 2021)
This dissertation examines the process by which a singular Ukrainian Canadian identity was constructed and entrenched throughout the twentieth century. It details how one of Canada’s largest and best organized diasporic communities, utilizing changing notions of cultural pluralism and the politics of the Cold War, crafted an increasingly nationalist, anti-communist version of identity that eradicated previously popular articulations of what it meant to be a Ukrainian in Canada. The traditional historiography posits that the community defined itself on its own terms, relying on individualized acts of agency and migrant resilience to entrench a version of Ukrainian-ness that was a democratic, bottom-up reflection of the collective. This project offers an alternative perspective by focusing on the battle over community narratives between communists, represented by the Ukrainian Labour Farmer Temple Association (ULFTA) and then the Association of United Ukrainian Canadians (AUUC), and the nationalists, organized under the umbrella of the Ukrainian Canadian Committee (UCC). I show how, with the help of state officials, the nationalists overpowered their ideological enemies on the left, concreting their identity as hegemonic. Through this process of coherence, they further bound specific aspects of their own ideology, perceived as innocuous, apolitical, and simply common sense, into mainstream political consciousness. Beyond a simple community study, this dissertation is also a case study about the building of anti-communist hegemony in Canada. Chapter One examines the role of state surveillance and political policing to show how state officials collaborated with the UCC to weaken the domestic left. Chapter Two analyzes the rise and fall of a government bureaucracy that acculturated the nationalists so as to embed them in Canada’s structures of power and bolster their anti-communism. Chapter Three looks more closely at acts of anti-communist violence, which seriously deterred participation in the AUUC. The state’s refusal to condemn the violence also telegraphed its preferences and helped define Canada’s social, political, and judicial boundaries. Chapter Four focuses on the nationalists’ appropriation of cultural pluralism to further entrench their version of Ukrainian identity. Lastly, Chapter Five explores commemoration, where competing visions for certain cultural figures were articulated and, eventually, nationalist narratives were set.
Keywords: Canadian history; Communism; Ethnicity; History; Migration; Nationalism; Politics; Ukrainian Canadian

«L'heure des pétitions est passée, il faut des actes» : les sans-travail et la protestation au Québec durant l'entre-deux-guerres (1919-1939) - Marsan, Benoit (Université du Québec à Montréal, 2021)
« L’heure des pétitions est passée, il faut des actes » présente une histoire vue d’en bas des sans-travail québécois au cours de l’entre-deux-guerres (1919-1939). L’objectif de cette thèse est de démontrer la contribution de l’action collective des sans-emploi à la politisation du problème du chômage au Québec durant les années 1920 et 1930. Cette période est un événement matrice pour l’histoire du chômage au Québec et au Canada. Le chômage, qui est déjà un phénomène important au cours du processus d’industrialisation au XIXe siècle, atteint au cours de la Grande Dépression des proportions jusqu’alors inégalées. Ce problème, qui jusqu’à la Première Guerre mondiale est encore largement considéré comme relevant d’une éthique du travail déficiente, de l’imprévoyance des individus, ou encore la conséquence des cycles saisonniers de l’économie, se présente de plus en plus comme un phénomène politique et systémique remettant en cause l’organisation de la société québécoise et canadienne. Dans ce changement de paradigme, l’action collective des sans-travail joue un rôle déterminant. Grâce à celle-ci, le chômage prend la forme d’un problème à la fois collectif, social et politique, qui ultimement remet en question la relation entre la démocratie et le capitalisme. L’étude du répertoire d’action collective des sans-travail québécois permet de mieux comprendre leur rôle dans l’histoire du chômage. Leurs protestations prennent racine dans une économie morale qui annonce une redéfinition de la citoyenneté fondée sur la formulation de nouvelles attentes envers l’État. Considérant que le chômage est indépendant de leur volonté, les sans-emploi estiment alors avoir le droit à une assistance contre le chômage. Bien que les manifestations de sans-travail ne soient pas un phénomène nouveau dans l’histoire québécoise, au cours des années 1920 et 1930, celles-ci apparaissent de moins en moins marginales. Prenant racine à Montréal dans le contexte de la Révolte ouvrière, elles s’étendent à plusieurs autres villes de la province au cours de la Grande Dépression. Perçus comme une menace à la paix sociale, dans un moment fortement marqué par l’anticommunisme, ces mouvements forcent les pouvoirs publics à intervenir. Encore peu étudiées à ce jour, ces manifestations, jumelées à celles qui se déroulent ailleurs au Canada, expliquent pourquoi le chômage devient, pour la première fois, un problème politique d’importance et débattu au sein de la sphère publique.

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Queen's University, 2021)
Beginning just a long decade after New France became part of the British Empire in 1763, a half-century of major crises engulfed British North America; the American Revolutionary War (1775-83), the postwar forced migration and resettlement of thousands of destitute and hungry British-American Loyalist refugees (1784-86), and the War of 1812 (1812-1814). In order to surmount, indeed, just to survive these crises, the British colonial regime in Quebec found it necessary to seek and retain the services of thousands of skilled, native-born, French-Canadian (Canadien) inland mariners in the newly acquired colony. For more than half a century, the Canadiens were needed to fulfill a variety of essential roles. Small boat (batteau) crews hauled virtually all the necessary supplies, including food, to sustain war and resettlement efforts west of Montreal for British soldiers and sailors, Loyalist settlers, militiamen, Indigenous allies and refugees. Canadien mariners also constructed, commanded, and crewed British warships on the Great Lakes. Some men were disabled in combat or became prisoners-of-war. Others died in shipwrecks or drowned on the river. The mariners left few personal records, but their actions were critically important for the successful defense and retention in the British Empire of the colonies that would eventually form central Canada. The contributions of Canadien inland mariners deserve serious consideration when examining the relationships between the people of the former New France and their new British rulers during the challenging, early transitional years of the British colonial regime.

Beyond the Railway Narrative: Exclusion and Agency in Chinese Canadian History Before 1947 - Oliver, Diane Christine (Saint Mary's University, 2021)
This thesis examines the role of Chinese in Canadian history by looking beyond the popular railway narrative that reinforces a stereotype of docile cheap labour and a reductive lens of racism. The research will look at what brought Chinese sojourners to Canada and the economic and legislation restraints and discriminatory labour practices by the government and employers. It will look at how Chinese people began to resist the prohibitive social, economic, and political policies through protests, Chinese unions, and collaborative efforts of Chinese and white Canadians. The railway narrative rendered Chinese women invisible within Canadian history as it focuses on the racial discrimination of Chinese men. The research will show Chinese women were impacted economically and socially by their lack of visibility within society due to gender and cultural discrimination by both white and Chinese communities. Finally, without acknowledgement and education the perpetuation of racial stereotypes will continue.

Paycheques & Paper Promises: Coast Salish and Mi’kmaw Work And Family Life under Canadian Settler Colonialism - Osmond, Colin Murray (University of Saskatchewan, 2021)
Using Community-Engaged research and an intersectional approach, this dissertation examines and interprets the ways two different Indigenous communities – The Tla’amin of British Columbia and the Mi’kmaq of Pictou, Nova Scotia –responded to the challenges and opportunities associated with settler colonialism, the creation of Indian Reserves, and the establishment of a capitalist wage labour economy in Indigenous territories. It primarily situates this discussion within the context of colonial efforts to geographically anchor Indigenous families in specific places while they struggled to retain meaningful connections with their broader territories. This dissertation provides critical analysis of the utility of using ‘settler colonialism’ as a catch-all to explain the various types of colonialism that impacted Indigenous people in Canada. Various types of colonialism contributed to a process where Atlantic Mi’kmaw and Pacific Coast Salish people with complex understandings of their territories and resources based on seasonal procurement and kinship systems, became geographically anchored on reserves as part of Indian Bands in the late nineteenth century. Within this confusing and often contradictory colonial world, the Tla’amin and the Mi’kmaq built adaptive and flexible economies that emphasized multiple occupations and relied on labour inputs from women and men to function. I argue that these new markets for Indigenous labour and commodities played an as of yet underappreciated role in the historical understanding of Indigenous motivations for securing specific reserve lands during the colonial survey of Indigenous lands in Canada. This dissertation adds to a growing body of literature that celebrates and historicizes Indigenous contributions to the labour history of Canada, and does so in ways that express how Indigenous people developed dynamic and responsive economies within emerging settler colonial economies in the nineteenth and twentieth centuries.

Towards a Critical History of The Writers' Union of Canada, 1972-1992 - Ramlo, Erin (McMaster University, 2021)
The Writers’ Union of Canada was founded in November of 1973 “to unite Canadian writers for the advancement of their common interests.” Drawing on extensive archival collections – from both the Writers’ Union and its member authors – this dissertation offers the first critical history of the organization and its work, from pre-founding to the early 1990s, arguing that the Writers’ Union has fundamentally influenced Canadian literature, as an industry, as a community, and as a field of study. I begin by tracing the contextual history of the organization’s founding, interrogating how union organizing, celebrity, and friendship underpin the organization’s work. Chapter One discusses the Writers’ Union’s programs, reforms, and interventions aimed at ‘fostering’ writing in Canada as I argue that the Union was instrumental in building a fiscal-cultural futurity for CanLit. In Chapter Two, I consider the role that women played in this important work, as I highlight the labour of female Union members and the all-female administrative staff, who maintained and supported the organization’s work through its first twenty years. In Chapter Three I draw attention to the stories of, perspectives of, and experiences of BIPOC authors in relation to the Writers’ Union. While the Writers’ Union’s involvement in race relations is often positioned as having ‘begun’ with the Writing Thru Race conference in 1994, this chapter uses the archives to reveal a much longer trajectory of racialized conflict within and around the organization, providing important context for the very controversial and public battles about appropriation and race that would explode in the late 1980s and early 1990s. Throughout this work, I look to see how institutional narratives are deployed and upheld, and to what ends; how successful advocacy work is often effaced and forgotten; how institutional structures function; and how their boundaries and intentions are challenged and developed over time.

The Provincial Workmen’s Association of Nova Scotia, 1879-1898 - Reilly, Sharon M. (Dalhousie University, 2021)
This thesis examines the history of the Provincial Workmen's Association of Nova Scotia, from iits formation in 1879, until the resignation of the union's first Grand Secretary in 1898. The study begins with a description of the economic background of the province's coal trade during the 19th century. The end of the "golden age" of wood, wind and sail, and the region's attempts to industrialize in response to the National Policy are discussed in relation to the coal industry. The difficulties experienced by tlthe miners as a result of these changing economic conditions are considered in the second chapter, and the formation of the P.W.A. is described. The early organizational activitities, constitution, ritual and structure of the society are also detailed. The following chapter investigates the three tactics employed by the P.W.A. to protect the rights and improve the condition of the Nova Scotia miners. The utility and ideological underpinnings of each method - strikes, governmennt lobbying and electoral politics - is considered in order to clarify the degree of success achieved by the union in its stated goals. Chapter Four focuses more directly on the idtdeology of the P.W.A. "Loyalist" and "rebel" attitudes toward the coal masters, the increasing alientation of the mine1ers from their work resulting from the development of industrial capitalism, and the growth of trade union consciousness and working class awareness are described. The influence of Robert Drummond on the Nova Scotia miners is also discussed. The fifth and final chapter describes the rank and file disconterent with leadership that emerged in the late 1880s and culminated with the company store dispute in 1896. The "invasion of thee Knights of Labor" and the resignation of Robert Drummond are examined. Final conclusions are then presented, followed by an epilogue, which describes briefly the path taken by the P.W.A. from 1898 until the dissolution of the union in 1917.

Trade Union Decline and Renewal: A Case Study of Precariousness, Labour Standards, and Union Responses in Ontario's Unionized Supermarket Sector - Rogers, Sarah (York University, 2021)
There is now a vast scholarship that explores union decline and renewal in various economic sectors and workplaces. To date, however, there is little understanding of how union decline has impacted unionized retail environments in Canada. Using a feminist political economy framework, this dissertation explores dynamics of union decline and renewal through a case study of labour standards in Ontarios unionized supermarket sector. Drawing on qualitative interviews with 28 union representatives and an analysis of collective agreements, this study examines the decline and trajectory of labour standards in unionized supermarkets, explores the unions perspectives and responses to changing standards, assesses how changing labour standards reflects the problem of union decline, and assesses how the case of Ontarios unionized supermarkets informs union renewal research and strategy. Findings suggest that the decline and trajectory of labour standards in Ontarios unionized supermarkets reflects a shift towards increasing precariousness in this sector. While there have been some wins for supermarket workers, unions have been largely unable to secure substantial improvements through collective bargaining. The precariousness associated with supermarket work is both contractually negotiated, as evidenced by provisions in collective agreements that ensure low wages and minimal and infrequent wage increases, demanding availability requirements, and limitations to the number of hours of work, as well as experiential, as indicated in workplace dynamics such as competition between workers, high turnover, and reduced health and safety measures. During the period under study, several factors have contributed to the increase in precariousness in this sector. While unions have implemented a variety of strategies in an effort to mitigate precariousness in unionized supermarkets, the persistence of deeply ingrained business union cultures and practices make improving labour standards through collective bargaining difficult. Continued precariousness in unionized supermarkets and the persistence of business unionism point to the need for an interrogation of the cultures and practices within unions that may contribute to the ongoing precariousness in unionized supermarkets and the challenges facing unions in this sector. The complex nature of union decline in this sector also suggests that multiple forms of union action are required to improve labour standards in unionized supermarkets and the strength of unions more broadly.

To Bite the Hands That Feed: Control and Competition in Temporary Foreign Worker Programs Amidst a Pandemic - Sevilla Valenzuela, Victor (University of British Columbia, 2021)
Canada’s continuous reliance on temporary foreign workers to address its labour shortage and maintain its competitive advantage has resulted in a seasonal transnational workforce characterized by its precarious living and working conditions, cumulative legal disenfranchisement based on the lack of permanent status, and vulnerability to the ongoing pandemic. Despite the common portrayal of the Seasonal Agricultural Worker Program (SAWP) as a ‘model for migration management’ by governments and growers, a large body of academic publications has studied their precarious conditions in an attempt to explain the seeming contradiction between a highly-exploited workforce and the steady growth of willing participants. This project examines the exploitative practices embedded in the cycles of transmigration through a series of individual interviews with SAWP participants, scholars, and government officials. The central argument is that the differential treatment of migrant and citizen workers lies at the heart of the former’s precarity. It stems from the paradoxical promotion of human rights at the macro-level, while relying on an exploited workforce at the micro-level. The program creates mechanisms that keep workers in a state of continuous marginalization despite decades of participation in the program. The legal, subtle, and overt mechanisms that maintain workers in a continuous state of control and competition are among the key findings of this project. This project challenges the idealization of the SAWP by analyzing the main beneficiaries, its shortcomings, and its projected future. It presents a unique opportunity to reimagine temporary foreign worker programs and methodological nationalism in a globalized context.

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon Thomas (University of Toronto, 2021)
This dissertation explores the points of tension between dominant histories of neighbourhood activism in Toronto and Montreal between 1963-1989 and the lived experiences of locally embedded activists who organized for access to safe jobs, homes, and the right to exist in their neighbourhoods. It demonstrates how material conditions, determined by the overlapping processes of deindustrialization, post-industrial development, and the movement of capital from Montreal to Toronto, shaped how neighbourhood activists organized, who they organized with, what they organized for, and how they recorded what they were doing. Dominant narratives of neighbourhood activism during this period over-emphasize the perspectives white, middle-class, and cis-gendered male activists who benefitted from the world the sixties made. Their upward mobility, made possible through the expansion of public spending and their involvement in gentrification, gave them the time and resources to document what they were doing, elevating their perspectives in the historical record. At the same time, embedded poor and working-class, racialized, disabled, and trans activists who continued to experience the ongoing structural violence of the capitalist city also continued to collectively resist that violence. Unfortunately, their ongoing precarity denied them of the resources necessary to produce historical records to the same degree as their upwardly mobile contemporaries. By historicizing how uneven material conditions shaped what activists were doing and how they recorded what they were doing, this thesis demonstrates how power shaped the production of neighbourhood activism history. It also presents opportunities to contest this power in the historical record.

Sewing in Arviat: Inuit Women’s Work Through Stories and Parkas - Williamson, Christina (Carleton University, 2021)
Sewing has long been a core part of Inuit women's land-based labour in Arviat, Nunavut. The objects that Inuit women produce by sewing, such as parkas, embody their responses to and perspectives of colonialism and the entrenchment of the capitalist economy in their communities. This dissertation takes an interdisciplinary approach using archival records and photographs, museums objects, interviews with seamstresses and experiential learning. In this project, gendered work is inherently connected to gendered knowledge. The amauti, a women's parka with a pouch to carry small children is useful for understanding both work and knowledge because it is a tool for women's work, while also serving as a conceptual lens through which to discuss Inuit women's knowledge transmission. I use methodologies developed in material culture studies to carefully develop three case studies to trace Inuit women's labour through three sewing mediums. The first case study uses caribou skin parka designs to examine women's responses to shifting patterns of subsistence and contact with First Nations and Qallunaat. This chapter argues that changes in caribou skin parka designs embody Inuit women's work as they render changes in their designs to respond to changes in their worlds, thereby enabling the continued work of all family members. Ann Meekitijuk Hanson's concept of Inuktization underpins the next two chapters. One examines the use of trade commodity beads, to centre the decisions of Inuit seamstresses as they undertake the physical and intellectual labour that resulted in beadwork that reflects Inuit aesthetics and worldviews. In the final case study, I argue that the shift to fabric parka sewing in the twentieth century demonstrates that sewing remains a significant part of women's work in the mixed economy of Arviat. Inuit women Inuktized fabric into something that suited their needs despite the deprivations caused by colonial policies. The findings of this project foreground Inuit women's work in historical records by centring the sewn objects that women make; they use their knowledge and skills to create a distinctly Inuit modernity.

(End)Zones and (Out)Fields of Production: Contemporary Conditions of Labor and Artistic Critique - Anderson, Stephanie (Western University, 2020)
In a 2013 exhibition publication titled It’s the Political Economy, Stupid!, John Roberts made the observation that “Over the last ten years we have become witness to an extraordinary assimilation of art theory and practice into the categories of labor and production.” Whereas once art claimed for itself a critical capacity in relation to the larger system of capitalist domination by its status as a putatively ‘autonomous’ sphere of production from which it leveraged its difference and critique, today it is largely acknowledged that there is no longer any such ‘outside’ to be aspired to. If, in the recent past, the immaterial, informational, creative, experiential, and affective elements of conceptual art were seen as potential resistant forces, in our current climate, where these forms of labor have become the dominant mode of production for the capitalist economy, these potentialities are now being widely questioned. With these developments in mind, this dissertation consists of a series of integrated articles that focus on the increasingly diffuse and interconnected circuits of global exchange and labor as they interact with specific sites and interventions of contemporary artistic production. In this, they coalesce around a general binding inquiry: does artistic labor today have the capacity to function as a critique of the (transforming) mechanisms of control and exploitation characteristic of capitalism in the twenty-first century? And if not, what does that entail about the continued political viability, and persisting social functions of contemporary artworks? Drawing on autonomist Marxist thought, the sociology of work and labor, performance studies, and critical readings on the relationship between artistic labor and recent forms of capitalist production, the chapters are organized around exhibitions and artworks which represent, critique, or (re)produce the conditions of production in late capitalism, while situating these within a global economy characterized by an uneven network of productive relations. In so doing, they trace the trajectory of labor relations and production practices as they have transformed over the last half decade through artworks and exhibitions that engage specific emblematic sites of production—the factory, the prison, and the museum (or amalgams of these spaces), and attempts to tease out places where reflection on the relationship between ‘artistic’ and ‘non-artistic’ labor in each may lead to clarity regarding the socio-political efficacy of contemporary art in an increasingly saturated and complex economic infrastructure.

Analyse critique de l'extractivisme comme mode de développement nordique à partir du cas de l'exploitation du minerai de fer au Québec - Bédard, Samuel (Université du Québec à Montréal, 2020)
Ce mémoire de maîtrise traite du rapport qu’entretiennent les grandes entreprises minières avec les collectivités locales, dans un contexte nordique. À partir du cas québécois de l’exploitation du minerai de fer, nous tentons d’apporter un éclairage nouveau à l’idée communément admise selon laquelle l’implantation, sur des territoires enclavés, de grands projets extractifs, constitue un vecteur de développement régional important. La démarche d’économie politique proposée prend pour objet les modes de gestion des ressources humaines et financières privilégiés dans le secteur minier de la Côte-Nord. Les données recueillies dans le cadre d’une analyse documentaire et d’une série d’entretiens semi-dirigés, menés à l’hiver 2019, convergent vers la thèse suivante : la diminution des retombées économiques constatée dans cette région est attribuable à la déterritorialisation de l’organisation contemporaine du travail dans les mines ainsi qu’à l’émergence de stratégies de restructuration épousant la dynamique du cycle de commodités.

Temporary Foreign Work, Precarious Migrant Labor and Advocacy in Canada: A Critical Exploratory Case Study - Brown-McLaughlin, Simone (University of Alberta, 2020)
Over the past forty-seven years, thousands of temporary foreign migrant workers have been arriving in Canada annually, to labor in sectors of precarious work including farming, caregiving and the service sector given the demand from employers seeking cheaper sources of labor or for work that Canadians are not available to do or are unwilling to do. Given the context of 21st century neoliberal capitalist globalization which has transformed the international division of labor, there has been an increase in the demand for migrants as a flexible source of cheap labor. Canada’s dependence on migrant workers has been facilitated through bilateral and unilateral programs with countries of the Global South to provide a steady stream of workers for its workforce. The purpose of this research was to critically explore and develop an understanding of precarious migrant worker exploitation and concerns pertaining to the Temporary Foreign Workers Program (TFWP) in Canada to inform advocacy undertaken by migrant organizations. Utilizing a race-gendered neo-Marxist perspective on capital and migrant labor a case study strategy was adopted and developed pertaining to the Seasonal Agricultural Workers Program (SAWP) and the Caregivers Program. Data collection included in-depth and focus group interviews with 17 farm and caregiver migrant workers and advocates, document reviews and analysis of web materials. Thematic analysis suggests temporary migrant work is marked by coercion, misrepresentation of contracts and bonded contractual arrangements. Migrant work and living in Canada are characterized by increasing levels of labor unfreedom experienced as domination, subordination, and race-gendered exploitation. Temporary foreign migrant workers are being driven further into debt, endure substandard working conditions and a social experience in Canada marred by prejudice, discrimination, and oppression. These preliminary critical exploratory findings inform advocacy work for migrant workers by contributing to new ways of "knowing and doing” and to challenge existing predatory precarious migrant work policies, processes, and experiences in Canada and internationally.

Le syndicalisme entre deux âges : le mouvement ouvrier à Québec et Lévis, 1896-1914 - Cadieux, Alex (Université d'Ottawa / University of Ottawa, 2020)
Dans notre thèse, nous étudions la période de « flottement » et de réorganisation du mouvement ouvrier entre le déclin de l’organisation des Chevaliers du Travail et l’ascension du syndicalisme catholique. Notre étude révèle que cette expérience de transition, entre les années 1896 et 1914, est formatrice pour le mouvement ouvrier de Québec et Lévis. L’analyse de ces années s’avère essentielle mieux saisir et caractériser la suite des évènements dans le monde syndical de cette région. Notre regard nouveau sur le mouvement ouvrier de Québec et Lévis permet d’éclairer le rôle actif des travailleurs et de nuancer le misérabilisme contenu dans une partie de l’historiographie ouvrière. En effet, nous montrons que les travailleurs de Québec et Lévis s’activent dans le monde du travail, mais aussi sur la scène politique, entre 1896 et 1914 afin d’améliorer leurs conditions de vie et de travail. Notre thèse indique aussi que, contrairement au contexte montréalais, Québec devient le bastion du syndicalisme national durant cette période. Cette conjecture peut trouver racine dans la relation particulière qui se développe à Québec et Lévis entre les patrons, la classe ouvrière et l’Église. En effet, l’Église de Québec et Lévis se montre un acteur important entre 1896 et 1914 ; la classe ouvrière doit ainsi négocier avec cette dernière pour se développer. Notre analyse permet ainsi d’expliquer le cheminement particulier des ouvriers de Québec et Lévis entre 1896 et 1914 et de mieux saisir leurs idéologies et leur conduite.

Mining Ontario: Corporate Power, the Mining Industry, and Public Policy in Ontario - Corbeil, Matthew Joseph (York University, 2020)
This dissertation critically examines the history of the government of Ontarios policies towards the mining industry to analyze the impact of concentrated economic power on political processes in liberal democracies. It is the first comprehensive study of the political power of one of the provinces largest and most influential industries. Drawing on critical theories of business power, this dissertation examines policy developments across four contentious issue areas, namely fiscal policy, air pollution control, occupational health and safety, and access to mineral lands. Employing a qualitative historical narrative, the study draws on data collected from the Public Archives of Ontario, newspapers, published reports and secondary academic literature. Challenging those theoretical perspectives that downplay the direct influence of large business enterprises over public policy, this dissertation argues that the mining industry has exercised a predominant influence over the government of Ontarios public policies. While the industry disposes of several political resources that privilege it in relation to its opponents, two in particular deserve special attention: First, minings commanding economic presence in the provincial North where alternative investment opportunities are generally absent, and second, the industrys deep-seated linkages with the provincial mining ministry in terms of personnel and ideology. In sum, the mining industrys structural power over the Northern economy together with its close working relations with the provincial ministry of mines have rendered provincial policymakers particularly vulnerable to the industrys lobbying, allowing the industry to play a predominant, though not monolithic, role in shaping provincial public policy.

Uncertain Future, Unsettled Present? Everyday Geographies of Precarious Immigration Status in Toronto, Canada - Dennler, Kathryn Elizabeth (York University, 2020)
Increasing processing times for immigration applications and increasing numbers of people admitted on temporary visas mean that more newcomers spend longer periods of time living in Canada with restricted rights and uncertain if they will be able to remain. This has contributed to an increase in precarious immigration status, which refers to a sense of insecurity caused by ones formal immigration status. The purpose of the dissertation is to examine how people are affected by living for prolonged periods of time with uncertainty about future residence and how these effects vary across space and time. The study, based on qualitative research with migrants in Toronto and people who work on migration issues, investigates how immigration status is performed in everyday life and how immigration status intersects with other social relations to produce distinctive affective textures of life in Toronto. The research shows that formal immigration status affects people differently depending on their migration motivations, capacities, and community support networks. Lack of reliable information about the time required to become eligible for permanent residence and application processing times make it more difficult for people to make decisions about how to orient themselves towards the future, the present, and the passage of time in ways that meet their needs. It identifies two salient temporal orientationssuspending or embracing engagement with everyday lifeeach of which comes with benefits and risks. Finally, the research suggests that contemporary practices of immigration control can lead to an internalization of discourses that construct people with precarious immigration status as unworthy of membership in Canadian society. Participants sought to undermine these discourses through narrative redefinition of themselves as people who have something to contribute but are stopped from doing so. I find that this resistance is necessary to peoples ability to persist, yet it has a limited effect on the harm done. The research findings contribute to scholarly understandings of formal immigration status and the slow violence of living with precarious immigration status.

Le Conseil général de la CEQ et l’arrimage de l’éducation à la souveraineté du Québec, 1990-1995. - Derradji, Fabrice (Université de Montréal, 2020)
Notre doctorat est une recherche sur l’histoire du syndicalisme enseignant au Québec durant la première moitié des années 1990. Plus précisément, du Congrès de la Centrale des enseignants du Québec (CEQ) de juin 1990 à la convocation par le ministre de l’Éducation du gouvernement Parizeau des États généraux sur l’éducation en mars 1995. Notre recherche s’efforce de poser des jalons pour une première histoire critique du syndicalisme des enseignants à construire dans son rapport à l’histoire de l’éducation selon un constat initial que la première est sous-évaluée, voire largement invisible dans divers champs des sciences humaines et sociales (Relations industrielles, sociologie et histoire). La CEQ est la centrale syndicale des fédérations et des syndicats locaux représentant des enseignantes et des enseignants du Québec (des secteurs primaire, secondaire, collégial et même universitaire) et des professionnels de l’enseignement (animateurs de pastorale à l’époque). L’organe décisionnel de la CEQ est le Congrès national qui se réunit tous les deux ans ; l’application des décisions du Congrès se fait à la fois par le Bureau national (Conseil exécutif à partir de juin 1992) et le Conseil général des délégués de toutes les fédérations et de tous les syndicats locaux affiliés à la Centrale. Cette agora syndicale, qui se réunit six fois par année, est le cœur de la vie démocratique, tumultueuse, de la Centrale syndicale et étudie tous les rapports, les documents, les analyses, etc., qui lui sont soumis par le Bureau national / Conseil exécutif, l’unité de recherche de la CEQ ou divers comités. Dans un premier temps, notre thèse aborde le fait que le syndicalisme enseignant québécois est un objet historique inachevé et inabouti. Notre démarche tente de répondre à ce lien problématique entre historiographie et histoire. Puis, elle propose de nouveaux jalons pour une étude critique de cette histoire, notamment sur l’échec de la première tentative d’arrimage syndical de l’éducation à la souveraineté du Québec de 1977 à 1984. Mais alors, comment une centrale syndicale a-t-elle pu évoluer d’une opposition d’inspiration marxiste à toute tentative de réforme imposée de l’éducation et à un projet de souveraineté considéré comme conservateur et « capitaliste » portée par le PQ en 1977-1985 à iii une proposition d’une réforme globale, néolibérale, de l’éducation et un soutien à une souveraineté « sociale-démocrate » portée par le même parti politique en 1994-1995 ? Pour expliquer et comprendre ce paradoxe historique, nous allons étudier les nouvelles orientations stratégiques de la CEQ à partir du Congrès de juin 1990. Puis, dans un second temps, à partir d’archives syndicales – les procès-verbaux des réunions des délégués syndicaux au Conseil général de la CEQ –, notre étude historique porte sur le second arrimage de l’éducation fait par la Centrale à la conquête de la souveraineté du Québec, et particulièrement le rôle que joua le Conseil général des délégués syndicaux quant à la définition de quatre positions : 1) la question de la déconfessionnalisation, puis de la laïcité du système éducatif québécois ; 2) l’élaboration de la politique d’éducation interculturelle ; 3) les enjeux politiques et stratégiques autour de la définition de la souveraineté du Québec ; 4) le tournant participatif et la proposition d’une réforme globale de l’éducation au Québec. Enfin, notre recherche historique nous amène à décrire les mémoires syndicales enseignantes qui font de la CEQ une centrale syndicale si particulière dans l’histoire du mouvement ouvrier québécois.

“The CCF Is Not a ‘Class’ Party”: Labour, Politics, and Their Unification at the Lakehead, 1944-1963 - Duplessis, Nicholas James (Lakehead University, 2020)
This study analyzes the new sophistication of the organized labour movement and labour’s relationship to politics in a period of rapid change for the Lakehead. ““The CCF is not a Class Party”” argues that, between 1944 and 1963, the organized labour movement and the Cooperative Commonwealth Federation (CCF) at the Lakehead underwent parallel structural developments against the backdrop of conservative social forces in the postwar period that, by the end of the 1950s, necessitated a merger of the two formally distinct entities. The amalgamation of labour and politics, resulting in the formation of the New Democratic Party (NDP), is best examined through the political career of Douglas Fisher, who first represented the CCF and, later, the NDP in Port Arthur. The debate surrounding the ‘New Party’ idea in the late 1950s at the Lakehead is reflective of the uneasy relationship between labour and politics that had formed throughout the postwar period.

Work and Worth: A Contested History of Labour and Value in Toronto’s Public Libraries - Frederiksen, Lia (University of Toronto, 2020)
Public libraries are often thought of as inherently democratic institutions where the provision of informational resources supports social inclusion and civic participation. Inspired by a recent citywide conflict over potential library closures in Toronto, Canada, this dissertation investigates a more contested history than conventional interpretations have often permitted by revealing a series of conflicts over public library buildings, budgets, and governance across more than a century. The main argument is that understanding this history requires an account of the overall work done to make and remake these spaces into what they are today, as a way of understanding of what these spaces may soon become. This argument illustrates how the perceived worth of providing public library service, whether or not it is accounted for in monetary terms, can be seen as socially constructed and politically contested. To make this argument, I draw mainly from feminist theorizations of work, which broaden this category to encompass productive waged labour along with paid and unpaid reproductive labour coded as ‘nonwork’ or ‘unproductive’, and geographers’ insights on the contested social production of space. In so doing, this dissertation aims for a critical re-thinking of what these spaces mean for daily urban life.

"Ni Rome, ni Moscou" : l'itinéraire des militants communistes libertaires de langue française à Montréal pendant l'entre-deux-guerres - Houle-Courcelles, Mathieu (Laval et Université Paris, 2020)
Cette thèse retrace l’itinéraire collectif d’un groupe de militants communistes libertaires de langue française pendant l’entre-deux-guerres à Montréal rassemblés autour d’Albert Saint-Martin (1865-1947). Figure importante du mouvement ouvrier au Québec, l’itinéraire politique de Saint-Martin est multiforme : on le retrouve associé au Parti socialiste du Canada, à la One Big Union, au Parti socialiste (communiste), à la Ligue des sanstravail, à l’Association révolutionnaire Spartakus, à l’Université ouvrière, à l’Association humanitaire, à la Ligue du Réveil féminin et à de nombreuses coopératives de consommation et de production. Saint-Martin est entouré de camarades provenant de divers horizons politiques. Notre thèse nous a permis d’identifier plus de 300 individus ayant pris part à des activités militantes à ses côtés. À travers l’analyse croisée de leurs parcours individuels, nous cherchons à mieux comprendre les modalités de leur engagement collectif avant, pendant et après la Première Guerre mondiale, leur représentation de la société idéale et les moyens d’y parvenir, la nature et la diversité de leurs liens de sociabilité, les territoires où se déploient leurs réseaux, la fréquence et les thèmes de leurs réunions de même que les symboles et les rituels qui y sont rattachés. Nous faisons l’hypothèse que celles et ceux qui participent aux activités de ce milieu partagent une même culture révolutionnaire articulée autour des notions de communisme, d’anticapitalisme, d’anticléricalisme et d’internationalisme, débouchant sur une critique des institutions autoritaires : l'État, l’Église catholique, la propriété privée, l’armée, le mariage, etc. Les stratégies d’émancipation individuelle et collective mises de l’avant par ces militants et ces militantes reposent sur l’éducation et l'action directe. C’est cet ensemble de principes théoriques, stratégiques et tactiques que nous regroupons sous le terme de communisme libertaire.

Making Prison Work: Prison Labour and Resistance in Canada - House, Jordan Lorne (York University, 2020)
This dissertation examines prisoner-worker organizing in Canada by considering three case studies in detail: first, the successful unionization of an experimental privately managed abattoir at the Guelph Correctional Centre, a provincial jail in Ontario, in 1977; second, efforts by federal prisoners to unionize, with a particular focus on the efforts by the Prisoners Union Committee in 1975 and the Canadian Prisoners Labour Confederation, between 2010-2015, and; third, the nation-wide federal prison strike in response to prisoner wage cuts in 2013. Through these cases, this study examines the similarities and differences between prisoner-workers and their non-incarcerated counterparts, and considers the methods and motivations of prisoner organizers, as well as the substantial legal and organizational barriers that Canadian prisoners face in their organizing efforts. Working prisoners are one of many groups who labour on the margins of society and the economy, and who have been largely overlooked or dismissed by both scholars of work and labour and the labour movement. This study seeks to expand conventional definitions of who is a workerand what constitutes the working classby demonstrating ways that prisoners have asserted their rights as workers and the legitimacy of their organizations and struggles. Through these struggles, which have been conceptualized not only as economic, but also as political struggles, prisoners have contested their state of privation and laid claim to new sets of rights. At their most successful, the organizing efforts of working prisoners have resulted in not only improvements to their working lives, but also expanded rights and freedoms in relation to their incarceration.

“Just Go to Work”: Gendered Harassment in Resource Extraction Work in Canada - Kelly, Griffin (University of Alberta, 2020)
This Master’s thesis examines tradeswomen’s experiences of and responses to gendered harassment at camp-based work in resource extraction industries in western Canada. This study predominantly features women working in the Alberta oil sands industry. Gendered harassment at work has been identified as a major issue in recent years (Curtis et al., 2018; Denissen, 2010; Wade & Jones, 2019) and this study aims to better understand tradeswomen’s day-to-day experiences of harassment in work camps. I utilize constructivist grounded theory methodology and critical feminist geography as the theoretical framework for the project. I find that tradeswomen employ a wide range of affective, material, and social strategies to manage harassment. I introduce two concepts, “just go to work” (JGTW) and “me vs. other girls,” to illuminate these strategies for self-preservation in the masculine occupational culture of work. This is labour that tradeswomen must perform in addition to their demanding work duties and schedules. JGTW demonstrates how gendered harassment is embedded into the masculinist culture of work of the trades. This study begins to address this gap in scholarly literature to capture the shifting cultural context of the oil sands industry and identifies new areas for future research.

Drowned: Anishinabek Economies and Resistance to Hydroelectric Development -in the Winnipeg River Drainage Basin, 1873-1975 - Luby, Brittany Alexandra (York University, 2020)
In 1893 the Keewatin Lumber and Power Company planned the first hydroelectric generating station on the north shore of Lake of the Woods (near present-day Kenora, Ontario). Approximately fifty years later, federal officials seeking employment for Canadian veterans turned to Northwestern Ontario and its underutilized water resources, envisioning a manufacturing hub on the Precambrian Shield. Between 1950 and 1958, the Hydroelectric Power Commission of Ontario remodeled the Winnipeg River drainage basin to produce power for federally-sanctioned peacetime industries, namely pulp and paper production. To redesign the Winnipeg River drainage basin, however, hydro officials needed to encroach on Anishinabek lands: both federally-recognized reserves and unrecognized, but heavily occupied, ancestral territories. This dissertation tells the story of how Anishinabek families used a diverse array of strategies adaptation, cooperation, and passive resistance to manage environmental change caused by Whitedog Falls Generating Station. Anishinabek families worked to stabilize their communities in an era of imposed environmental and economic change. Historians have long argued that hydroelectric development is necessarily at odds with Indigenous culture and subsistence economies. This dissertation provides a counter-narrative, arguing that cultural and economic damage, although linked to environmental damage, correlated more strongly with Anishinabek exclusion from resource negotiations. Moreover, this work complicates historical representations of a uniform Indigenous response to development. Given limited negotiations between the Hydro-Electric Power Commission and local First Nations, Anishinabek families did not respond to industrial incursions with one representative voice. The process of development itself, I argue, prevented a unified community response. As a result, Anishinabek communities fractured in response to hydroelectric development.

Serving Each Other: Sharing Economies and Affective Labour in Montreal’s Kiki Scene - Lundy, Jess D. (Jessica Dawn) (Carleton University, 2020)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal's Kiki scene and Ottawa's emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of 'each one, teach one', is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate non-normative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Just a Farmwife?: An Intergenerational, Intersectional Study of Women’s Labour on Southern Alberta’s Dutch Reformed Family Farms, 1950–2019 - Martens, Shelby Blair (University of New Brunswick, 2020)
Through two-part intergenerational oral histories, this thesis explores the intersections of labour, gender, and lived religion in the lives of twelve Southern Alberta, Dutch Reformed women from family farms from the 1950s to 2019. By focusing on the broader lived experience of the women interviewed, and not just their physical labour on the farm, this thesis argues that women’s roles on the family farm were crucial, while complicating the narrative of farm women’s roles to show their multiple and often conflicting identities.

Harms of Criminalization of Sex Work: How End-Demand Legislation and Immigration Policy Shape Labour, Health and Rights Among Im/Migrant and Indoor Sex Workers in Canada - McBride, Bronwyn (University of British Columbia, 2020)
Background and objectives: Globally, sex workers experience labour rights abuses, disproportionate burdens of workplace violence, and restrictions on safer ways of working (i.e., collectively and in indoor venues) due to criminalization. These inequities are often exacerbated among im/migrant sex workers, who may additionally face precarious legal status, restrictive immigration policies and racialized policing. Despite implementation of “end-demand” legislation (legal models aimed at ending clients’ demand for sexual services) in dozens of countries, little empirical research has explored how end-demand laws impact sex workers’ labour conditions. This dissertation sought to explore how end-demand laws and prohibitive immigration policy impact labour conditions, health and rights among im/migrant and indoor sex workers in Vancouver. Methods: This dissertation drew on quantitative and qualitative data collected from AESHA (An Evaluation of Sex Workers’ Health Access), a community-based open prospective cohort of 900+ women sex workers across Vancouver, Canada, who complete bi-annual interviewer-administered questionnaires and voluntary sexual health testing. Mixed methods (explanatory and confounder bivariate and multivariable logistic regression analyses; interrupted time series; coding of semi-structured interview data) were used to elucidate the impacts of end-demand laws and resulting law enforcement practices on indoor and im/migrant sex workers’ labour environments. Results: This dissertation found that end-demand legislation in Canada failed to improve sex workers’ access to justice, restricted access to supportive third parties and safer indoor venues, heightened the vulnerability of sex work venues to violence, and limited access to occupational health resources (condoms, community-led services); with negative implications exacerbated among im/migrant sex workers. Conclusion: These findings extend limited existing research on the impacts of end-demand legislation, and demonstrate that end-demand criminalization reproduces the harms of full criminalization models. These results have important implications for legislative, policy, and law enforcement reforms towards enabling safe labour environments among im/migrant and indoor sex workers. This dissertation calls for the decriminalization of sex work; removal of prohibitions on im/migrant sex work; sensitivity and anti-stigma trainings among authorities; dedicated efforts to address systemic racism in sex work policing; promoting rights-based municipal occupational health standards; and increasing support for sex worker-led outreach; to promote sex workers’ labour and human rights.

Connected by a Thread: Stories of Migration and Labour in Sara Angelucci’s Piece Work - Montpetit, Chiara (Concordia University, 2020)
This thesis is a critical analysis of the multimedia project Piece Work (2017) by Toronto-based, Italian Canadian artist Sara Angelucci (b. 1962). Focusing on Coppley Apparel, a garment factory in Hamilton, Ontario, the project explores the process of making business suits through the digital collage Coppley Patterns and the photographic series Mano d’Oro. The sound installation A Sewers’ Chorus features the voices of the garment workers who recall positive and negative memories of their work experiences and personal histories, while the video installation Suit Elevator depicts the business suit in its final form. The majority of Coppley Apparel’s employees are women from non-white racialized groups. Deploying an intersectional feminist approach, this thesis argues that Piece Work reveals the complex lives of these factory workers from immigrant backgrounds in ways that speak against persisting discourses and practices of racialized and gendered labour in the garment industry. It begins by providing an overview of the history of the Coppley Apparel factory in relation to the history of migrant garment factory workers in Hamilton, and the broader history of racialized and gendered factory labour in the city. This thesis also acts as a record of the migration story of Nina Acciaroli, the artist’s mother, whose first job in Canada was at Coppley Apparel. It then examines A Sewers’ Chorus and its use of oral history, providing a discussion of the different stories shared by the interviewees, which range from happy childhood memories and nostalgic flashbacks to accounts of traumatic experiences. The thesis provides a comprehensive discussion of the process of making Piece Work, contextualizing it within Angelucci’s larger artistic practice of incorporating voices in the exploration of her family’s immigrant experience. Ultimately, Piece Work recognizes the employees of Coppley Apparel as people with singular voices and unique experiences and highlights their agency by including the complexity of their voices and identities as women, garment workers, racialized minorities, and contributing members of Canadian society.

Organizing Canadian Theatre Designers: The Intersection of Creative and Precarious Labour - Moore, Conor (Simon Fraser University, 2020)
Canadian theatre designers share many similarities with other freelance, creative workers in Canada. The conditions of precarity that define their working relationships are similar to those that affect workers in other sectors, such as film, music, television, and visual arts. This thesis begins by examining the existing literatures and research concerning creative and precarious work, primarily in Canada, but also internationally. Drawing on in-depth interviews of 55 designers from within the relatively small community of Canadian theatre designers, approximately 500-700 workers, I examine the working conditions that designers find challenging and seek suggestions for how they can be improved. Additionally, I explore the different models that designers have used to organize in Canada, Quebec, and the United States. By comparing these models with the interviews from designers, I conclude that the best way for Canadian designers to improve their working conditions is to build a closer relationship with IATSE [International Alliance of Theatrical Stage Employees], the union that represents stagehands and technicians. Finally, I identify some questions for further exploration, including the tension between artistic and worker identities, while also touching on the present circumstances of the Covid-19 crisis and the current conversations concerning racism and white supremacy within Canadian society.

Beyond the Barbed Wire: POW Labour Projects in Canada during the Second World War - O'Hagan, Michael (Western University, 2020)
This dissertation examines Canada’s program to employ prisoners of war (POWs) in Canada during the Second World War as a means of understanding how labour projects and the communities and natural environment in which they occurred shaped the POWs’ wartime experiences. The use of POW labourers, including civilian internees, enemy merchant seamen, and combatant prisoners, occurred in response to a nationwide labour shortage. Between May 1943 and November 1946, there were almost 300 small, isolated labour projects across the country employing, at its peak, over 14,000 POWs. Most prisoners were employed in either logging or agriculture, work that not only provided them with relative freedom, but offered prisoners unprecedented contact with Canada and its people. Work would therefore not only boost production but, it was hoped, instil POWs with Canadian mores and values through interaction with guards, civilians, and the natural environment. Rather than attempt a narrative encompassing almost 300 labour projects, this dissertation examines POW labour through a series of five case studies. The first examines prisoners cutting fuelwood in Manitoba’s Riding Mountain National Park while the second and third examine POWs cutting pulpwood in Northwestern Ontario for the Ontario-Minnesota Pulp & Paper Co. and Abitibi Power & Paper Co., respectively. The fourth case study examines POWs employed by Donnell & Mudge in its tannery in New Toronto, Ontario and the fifth examines the practice of employing POWs in farm work in Alberta, Saskatchewan, Manitoba, Ontario, and Quebec. Through these case studies, this dissertation examines how how internment officials employed remote parts of Canada as a physical boundary to prevent escape attempts, while also using it as a space to provide POWs with relative freedom as an inducement to work, and how work challenged definitions of who or what was the “enemy”. With significantly more freedom than the typical internee, POWs interacted with civilians and guards on a more familiar level, resulting in illicit fraternizations and relationships between POWs and Canadians. Although such fraternization also triggered considerable protest, these interactions reveal a great deal regarding POWs’ opinions of and attitudes towards Canada and its people as well as Canadian attitudes towards POWs.

The Academic Librarian as the Subaltern: An Institutional Ethnography of a Feminized Profession - Revitt, Eva Justyna (University of Alberta, 2020)
I locate this study within the context of my own work and experiences as an academic librarian and the disconnect that I have often felt between what I consider my role and the value of my work to be versus the perception and understanding of that role, the work, and its value by others. Overwhelmingly, librarians working at Canadian universities are considered academic staff, if not faculty. However, the role and fit of the academic librarian within the academic enterprise is overshadowed and frequently misunderstood. As the subaltern, librarians’ expertise and contribution to the university’s academic mission is often sidelined: the nature of the work too frequently viewed through an organizational rather than an academic lens and characterized as preoccupied with a structured set of regularized responsibilities. The goal of this study is to make visible the processes that shape the work experiences of academic librarians such as they are. Two research questions served as the impetus for this study: How is it that the academic librarian’s lesser status is the ideal at Canadian universities? What are the social processes that shape this ideal? This study is informed by the epistemological, ontological, and methodological assumptions of institutional ethnography: a research approach developed by the Canadian social theorist and sociologist, Dorothy Smith. Institutional ethnography considers the everyday, lived experiences of people as the research problematic—a term used by Smith to focus the inquiry on the actual, social, and active world as it is lived and experienced by people. An institutional ethnography progresses through layers, in this case the progression is from the academic librarian, to the library, to the institution, and beyond, to reveal how power structures external to the local setting influence daily life. To understand how the everyday world is put together so that things happen as they do, the focus of the investigation is on individual experiences and what people are doing relationally. However, in institutional ethnography the actions and experiences of people within a particular setting are not regarded as representative. Rather, the local experience is regarded as a window into the role of power. It is a politically charged and activist type of scholarship. Because institutional ethnography is concerned with explicating the actual rather than formulating or advancing the theoretical, the emphasis is on discovery rather than hypothesis testing. The findings of this study reveal how the value of librarians’ work is socially constructed and based on work that is perceived as women’s work; how the work of librarians is organized as library work rather than academic work; how accreditation bodies and the professions privilege the library over the librarian; and how institutional policies and practices position the librarian as academic on the margins of the academy. These social processes reveal how things come about so that librarians’ experiences as academic staff are such as they are. However, it is ideologies that help us understand why things are the way they are. I propose that two ideological codes—women’s work and the library—permeate our social consciousness, including speech, text, and talk, and infuse librarians’ work with particularizing characteristics. Ultimately, the findings of this study tie librarians’ work experiences to the necessary and gendered exploitation of labour that happens within a capitalist mode of production.

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Concordia University, 2020)
Montreal’s garment industry was the largest in Canada until most of its factories closed or relocated in the 1980s and 1990s, but it did not go out quietly. Staring down the barrel of rapid, state-sanctioned deindustrialization, 9,500 members of the Quebec ILGWU, most of them immigrant women, launched an industry-wide strike in August of 1983, the first in 43 years, as well as the last. Using the strike as a springboard, this thesis combines oral history interviews and archival material with historical, geographical, and feminist literatures to understand how women workers experienced and contested garment deindustrialization in 1980s Montreal. The result is a graphic novel about garment work and feminist labour struggle, for public consumption. This thesis adds much-needed female perspective to a growing body of work around deindustrialization and its contestation within history and geography. Conceptually and politically, it seeks to recast the Mile End and Mile-Ex as a site of feminist, working-class struggle, placing gentrification in conversation with deindustrialization while offering a primer on place-based labour organizing during a time of unprecedented capital mobility.

Theorizing Precarization and Racialization as Social Determinants of Health: A Case Study Investigating Work in Long-Term Residential Care - Syed, Iffath Unissa (York University, 2020)
This thesis uses anti-racist and feminist political economy of health perspectives that intersect with immigrant status, in order to analyze the findings from a single-case study investigating the social determinants of health and work precarization in a residential long-term care (LTC) facility in Toronto, Ontario. Throughout this dissertation, I use mixed methods case study to investigate social, political, and economic implications in the lives of health care workers. Observation, interview, and survey methods were utilized to investigate workers health in relation to the precarization of work. Specifically, I used the concept of precarization as a lens to track the ways in which work relations impact the other social determinants of health. The main areas of focus include the intersections of gender, work, and occupational health with race, immigrant status, and culture; the ways in which precarization affects employees in this specific health care sector; the implications of precarization in the health and wellbeing of workers and their families; the role of (un)paid care work and social support provided by family members; and the exercise of strength, resilience, resistance, agency, and coping strategies. Broadly, I will argue that precarization in LTC is an increasingly experienced phenomenon, and that various levels of precarization are experienced by particular workers who are women, racialized persons, and immigrants. This study contributes to our understanding of racialization as a social determinant of health, and analyzes the health impacts of workplace inequality through the lens of precarization. The study makes the case for closer attention to racism and precarity both on and as social determinants of health.

Mapping Ruling Relations Through Homelessness Organizing - Withers, A. J. (York University, 2020)
Poor peoples organizing can be effective even in periods of neoliberal retrenchment. This dissertation examines ruling relations and the social relations of struggle from the standpoint of the Ontario Coalition Against Poverty (OCAP) in Toronto, Ontario, Canada. With political activist ethnography as my central theoretical framework and methodological approach, I conducted field research, interviews and textual analysis of City and organizational documents. Focusing on OCAPs homelessness campaigns, I examine the social relations of struggle in three campaigns in Toronto: a campaign to stop the criminalization of homeless people in a public park by private security, a campaign to increase access to a social assistance benefit for people in emergency housing need, and a campaign to increase the number and improve the conditions of emergency shelter beds. My research demonstrates the active and ongoing research and theorization that anti-poverty activists engage in as well as the practices of delegitimization, excluding critique, testimonial injustice and epistemic violence that ruling relations engage in to counter activist research and theory. Some of this research and theory has regarded both Housing First policy and philosophy and Torontos emergency shelter system which OCAP, homeless people and other advocates have been decrying as unjust and inept for years. This dissertation explicates some of the ways that the City works to delegitimize its challengers and demonstrates the validity of many of the longstanding critiques of the ruling regime. While the City of Toronto has worked to contain homelessness organizing in Toronto, and deployed numerous demobilization tactics to do so, each campaign was fully or partially successful. Full or partial victories were secured by anti-poverty activists through the use (or threat) of direct action tactics.